Novel diamine compound, polymer obtained using same, liquid crystal aligning agent, liquid crystal alignment film, and liquid crystal display element
By using a polyimide generated by polymerization of a specific diamine and a tetracarboxylic dianhydride, a liquid crystal orientation film with high voltage retention and film strength is formed, which solves the problem of low voltage retention and stable orientation of the liquid crystal display element at high temperatures. The problem of insufficient sexuality reduces AC afterimage and improves the performance of the liquid crystal display element.
Patent Information
- Application Number
- CN202380040199.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-13
- Filing Date
- 2023-05-10
- Publication Date
- 2024-12-27
AI Technical Summary
The liquid crystal orientation film of the existing liquid crystal display element has low voltage retention rate at high temperatures, and the orientation stability is insufficient in IPS and FFS driving modes, resulting in AC after image problems. The film loss increases after substrate thinning, making it difficult to meet high definition and high Performance requirements.
Using specific diamines as polymer raw materials, polyimides generated by polymerization reaction with tetracarboxylic dianhydrides form a liquid crystal alignment film with high voltage retention and film intensity, and the liquid crystal molecules are improved by photo-oriented treatment. Orientation stability.
The high voltage retention rate and high film strength of the liquid crystal oriented film at high temperatures are achieved, the AC afterimage is reduced, the performance and stability of the liquid crystal display element are improved, and the reduction of the polymer molecular weight is suppressed.
Smart Images

Figure CN119212979A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a novel diamine compound, a polymer obtained by using the diamine, a liquid crystal alignment agent, a liquid crystal alignment film and a liquid crystal display element. Background Art
[0002] At present, in most cases, a polyimide film is used for a liquid crystal alignment film used for a liquid crystal display element. The polyimide film is prepared by applying a polyimide precursor such as a solution of polyamic acid or a solution of a solvent-soluble polyimide to a substrate and calcining the solution. The polyamic acid or the solvent-soluble polyimide is usually synthesized by reacting a tetracarboxylic acid derivative such as tetracarboxylic dianhydride with a diamine.
[0003] Liquid crystal display elements include, for example: a liquid crystal layer sandwiched between an element substrate and a color filter substrate; pixel electrodes and a common electrode for applying an electric field to the liquid crystal layer; a liquid crystal alignment film for controlling the orientation of liquid crystal molecules in the liquid crystal layer; a thin film transistor (TFT) for switching the electrical signal supplied to the pixel electrode; etc. As a driving method for liquid crystal molecules, longitudinal electric field methods such as TN (Twisted Nematic) method and VA (Vertical Alignment) method are known; and transverse electric field methods such as IPS (In-Plane Switching) method and FFS (Fringe Field Switching) method are known.
[0004] At present, the most popular liquid crystal alignment film in industry is made in the following way, that is, the surface of the film formed on the electrode substrate, which is composed of a polymer represented by polyamic acid and / or polyimide imidized therefrom, is rubbed in one direction with a cloth such as cotton, nylon, polyester, etc., so-called friction treatment. Friction treatment is a simple and productive method useful in industry. On the other hand, with the high performance, high definition and large-scale of liquid crystal display elements, as an orientation treatment method replacing friction treatment, it is known that a photo-orientation method that imparts liquid crystal orientation ability by irradiating polarized radiation is used. As far as the photo-orientation method is concerned, a method utilizing photoisomerization reaction, a method utilizing photocrosslinking reaction, a method utilizing photodecomposition reaction, etc. are proposed (for example, refer to non-patent document 1, patent document 1).
[0005] In recent years, in mobile applications such as smart phones and in-vehicle applications such as in-vehicle navigation, it is required to be able to withstand long-term use in harsh environments. The liquid crystal alignment film used therein requires higher reliability than before, for example, regarding the electrical properties of the liquid crystal alignment film known as voltage retention, it is required that not only the initial properties are good, but also good properties are maintained after long-term exposure to high temperatures. As a method for solving the above problems, it is proposed in patent document 2 to use a diamine having a diaminodiphenylamine structure as a liquid crystal alignment agent for a polyimide (precursor) raw material.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 9-297313
[0009] Patent Document 2: WO2004 / 021076
[0010] Non-patent literature
[0011] Non-patent document 1: "Liquid crystal photo-alignment film" Kidowaki and Ichimura Functional Materials, November 1997, Vol. 17, No. 1113-22 Summary of the invention
[0012] Problems to be solved by the invention
[0013] As the definition of liquid crystal display elements increases, the level of the above-mentioned requirements becomes higher, and a liquid crystal aligning film that can satisfy the requirements at a high level is required.
[0014] In addition, in liquid crystal display elements for mobile applications such as smart phones and car navigation, the thickness of the substrate (e.g., glass substrate, etc.) constituting the liquid crystal panel is sometimes thinned from the perspective of lightweight. Therefore, from the perspective of suppressing the film loss of the liquid crystal alignment film that occurs with the thinning of the substrate, a liquid crystal alignment film with high film strength is sometimes required.
[0015] Moreover, in the IPS mode and FFS driving mode, the stability of the liquid crystal orientation is also very important. If the orientation stability is low, the liquid crystal cannot return to its original state when it is driven for a long time, which becomes the cause of reduced contrast and afterimage (hereinafter referred to as AC afterimage). Therefore, a liquid crystal orientation film that suppresses AC afterimage is also required.
[0016] The polyimide (precursor) obtained by using the diamine having a diphenylamine structure described in Patent Document 2 described above causes a significant decrease in the molecular weight of the polymer in the firing step when producing a liquid crystal alignment film, and thus the above-mentioned problems cannot be fully solved.
[0017] According to the above content, the first purpose of the present invention is to provide a novel diamine, a polymer obtained by using the diamine, and further, to provide a liquid crystal aligning agent, a liquid crystal aligning film obtained by the liquid crystal aligning agent, and a liquid crystal display element using the liquid crystal aligning film, wherein the liquid crystal aligning agent can obtain a liquid crystal aligning film with a high voltage retention rate even after long-term exposure to high temperature when using the polymer. In addition, the purpose is to provide a liquid crystal aligning agent, a liquid crystal aligning film obtained by the liquid crystal aligning agent, and a liquid crystal display element using the liquid crystal aligning film, wherein the liquid crystal aligning agent can suppress the molecular weight reduction of the polymer during the firing when making the liquid crystal aligning film. And the purpose is to provide a liquid crystal aligning agent, a liquid crystal aligning film obtained by the liquid crystal aligning agent, and a liquid crystal display element using the liquid crystal aligning film, wherein the liquid crystal aligning agent can obtain a liquid crystal aligning film with a high voltage retention rate, high film strength, and suppressed AC residual image even after long-term exposure to high temperature.
[0018] Solutions for solving problems
[0019] The present inventors have conducted intensive studies to solve the above-mentioned problems and, as a result, have found that a liquid crystal aligning agent containing a polymer having a specific diamine as a constituent component is extremely effective in achieving the above-mentioned object, thereby completing the present invention.
[0020] The present invention includes the following aspects.
[0021] 1. A diamine, wherein the following formula (d A -1)~(d A -6) in any expression.
[0022]
[0023] 2. A polymer, which is at least one selected from the group consisting of a polyimide precursor obtained using a diamine component containing the diamine described in 1 above and a polyimide which is an imidate of the polyimide precursor.
[0024] 3. The polymer according to 2 above, wherein the diamine component further includes a diamine having at least one group selected from the group consisting of a urea bond, an amide bond, a carboxyl group, and a hydroxyl group in the molecule.
[0025] 4. The polymer according to 2 or 3 above, wherein the diamine described in 1 above is used in an amount of 5 mol% or more based on the diamine component.
[0026] 5. The polymer according to any one of 2 to 4 above, wherein the polymer is obtained by a polymerization reaction of the diamine component and a tetracarboxylic acid component, and the tetracarboxylic acid component contains tetracarboxylic dianhydride or a derivative thereof.
[0027] 6. The polymer according to 5 above, wherein the tetracarboxylic dianhydride or a derivative thereof is a non-cyclic aliphatic tetracarboxylic dianhydride, alicyclic tetracarboxylic dianhydride, aromatic tetracarboxylic dianhydride, or a derivative thereof.
[0028] 7. The polymer according to any one of 5 to 6 above, wherein the tetracarboxylic dianhydride or its derivative is a substance as follows: a non-cyclic aliphatic tetracarboxylic dianhydride as 1,2,3,4-butanetetracarboxylic dianhydride; a substance selected from 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-dichloro-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-difluoro-1,2,3,4-cyclobutanetetracarboxylic dianhydride; butanetetracarboxylic dianhydride, 1,3-bis(trifluoromethyl)-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 3,3',4,4'-dicyclohexyltetracarboxylic dianhydride, 2,3,5-tricarboxycyclopentylacetic dianhydride, 4-(2,5-dioxotetrahydrofuran-3-yl)tetrahydronaphthalene-1,2-dicarboxylic dianhydride, 5-(2,5-dioxotetrahydrofuran-3-yl)-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 5-(2,5-dioxotetrahydrofuran-3-yl)-8- Alicyclic tetracarboxylic acid dianhydride selected from methyl-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic acid dianhydride, bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic acid dianhydride and 2,4,6,8-tetracarboxybicyclo[3.3.0]octane-2:4,6:8-dianhydride; selected from pyromellitic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, 3,3',4,4'-diphenylsulfone tetracarboxylic acid dianhydride, 1,4,5,8-naphthalene tetracarboxylic acid dianhydride, 2,3,6,7-naphthalene tetracarboxylic acid Aromatic tetracarboxylic dianhydrides selected from dianhydrides, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 2,2',3,3'-biphenyl tetracarboxylic dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)-2,2-diphenylpropane dianhydride, ethylene glycol ditrimellitic anhydride, 4,4'-(hexafluoroisopropylidene) diphthalic anhydride, 4,4'-carbonyl diphthalic anhydride, 4,4'-(1,4-phenylenedioxy)bis(phthalic anhydride) and 4,4'-(1,4-phenylenedimethylene)bis(phthalic anhydride); or derivatives thereof.
[0029] 8. A liquid crystal aligning agent, comprising the polymer according to any one of 2 to 7 above.
[0030] 9. The liquid crystal alignment agent according to 8 above, further comprising a polymer (B), wherein the polymer (B) is at least one selected from the group consisting of a polyimide precursor obtained by using a diamine component that does not contain the diamine described in 1 above and a polyimide that is an imide product of the polyimide precursor.
[0031] 10. The liquid crystal aligning agent according to the above 9, wherein the polymer (B) is obtained by a polymerization reaction of the diamine component and a tetracarboxylic acid component, and the tetracarboxylic acid component contains tetracarboxylic dianhydride or a derivative thereof.
[0032] 11. A liquid crystal alignment agent according to any one of 8 to 10 above, wherein the liquid crystal alignment agent further contains at least one additive selected from the following compounds: at least one cross-linking compound selected from the group consisting of a cross-linking compound (c-1) having the following substituents and a cross-linking compound (c-2) having a polymerizable unsaturated group; a functional silane compound; a metal chelate compound; a curing accelerator; a surfactant; an antioxidant; a sensitizer; a preservative; a compound for adjusting the dielectric constant and resistance of the obtained liquid crystal alignment film; and a compound for promoting imidization, wherein the substituent is selected from at least one of an oxirane group, an oxetane group, a blocked isocyanate group, an oxazoline group, a cyclocarbonate group, a hydroxyl group and an alkoxy group.
[0033] 12. A liquid crystal alignment film obtained from the liquid crystal aligning agent according to any one of 8 to 11 above.
[0034] 13. A liquid crystal display element comprising the liquid crystal alignment film according to 12 above.
[0035] 14. A method for manufacturing a liquid crystal display element, comprising the following steps (1) to (3).
[0036] Step (1): A step of applying the liquid crystal aligning agent according to any one of 8 to 11 above onto a substrate.
[0037] Step (2): A step of baking the applied liquid crystal aligning agent to obtain a film.
[0038] Step (3): a step of subjecting the film obtained in step (2) to an orientation treatment.
[0039] 15. The method for manufacturing a liquid crystal display element according to 14 above, wherein the alignment treatment is a photo-alignment treatment.
[0040] Effects of the Invention
[0041] When the diamine of the present invention is used as a raw material for a polymer constituting a liquid crystal alignment film, a liquid crystal alignment agent can be obtained, a liquid crystal alignment film obtained from the liquid crystal alignment agent, and a high-performance liquid crystal display element having the liquid crystal alignment film. The liquid crystal alignment agent suppresses the decrease in the molecular weight of the polymer during calcination and forms a liquid crystal alignment film with a high voltage holding ratio.
[0042] Moreover, when the diamine of the present invention is used as a raw material for a polymer constituting a liquid crystal alignment film, a liquid crystal alignment agent, a liquid crystal alignment film obtained from the liquid crystal alignment agent, and a liquid crystal display element using the liquid crystal alignment film can be provided, wherein the liquid crystal alignment agent can obtain a liquid crystal alignment film with high film strength, suppressed AC residual image, and high voltage retention even after long-term exposure to high temperature.
[0043] The mechanism for obtaining the above effects of the present invention is not necessarily clear, but is roughly estimated as follows: It is considered that the above effects are obtained by imidizing the aromatic tetracarboxylic dianhydride skeleton part which significantly reduces the molecular weight during calcination in advance, thereby suppressing the reverse reaction and the reduction in molecular weight caused by it. DETAILED DESCRIPTION
[0044] Hereinafter, the novel diamine, the polymer obtained using the diamine, the liquid crystal alignment agent containing the polymer, the liquid crystal alignment film formed using the liquid crystal alignment agent, and the liquid crystal display element having the liquid crystal alignment film are described in detail. The description of the necessary conditions recorded below is an example of an embodiment of the present invention and is not specific to these contents.
[0045] In the following description, examples of the "halogen atom" include a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, etc. "Boc" represents a tert-butyloxycarbonyl group, and "*" represents a bonding position.
[0046] (Specific diamine)
[0047] The diamine of the present invention is the following formula (d A -1)~(d A -6) is a diamine (0) (also referred to as a specific diamine in the present invention) represented by any formula.
[0048]
[0049] The method for producing the specific diamine of the present invention is not particularly limited, but a preferred method includes a production method including the following steps (i) to (iv).
[0050] <Step (i)>
[0051] The amino protecting agent such as di-tert-butyl dicarbonate is reacted with the following formula (d i-1) to obtain a compound in which the amino group is protected by a Boc group (d i -2). Here, Y in formula (i) represents a divalent organic group obtained by removing two amino groups from a diamine, and examples of the diamine include 4,4'-diaminodiphenylamine and 4,4'-diaminodiphenyl-N-methylamine.
[0052]
[0053] <Step (ii)>
[0054] Tetracarboxylic dianhydride and formula (d i -2) to obtain the following formula (d i -3) shown in the formula. Here, X in formula (ii) represents a tetravalent organic group obtained by removing two anhydride groups from tetracarboxylic dianhydride, and examples of tetracarboxylic dianhydride include pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, or 3,3',4,4'-biphenyltetracarboxylic dianhydride. In addition, Y in formula (ii) has the same meaning as in formula (i).
[0055]
[0056] <Process (iii)>
[0057] The above formula (d i -3) is imidized to obtain an imide compound (d i -4).
[0058]
[0059] <Step (iv)>
[0060] Make a mineral acid such as hydrochloric acid react with the above compound (d i -4) reaction, and deprotection reaction is performed to obtain the diamine compound of the present invention. The reaction temperature is not particularly limited, and the reaction can be carried out at 0 to 100°C.
[0061] In the synthesis reaction of the specific diamine, a solvent can be used as needed. As the above-mentioned solvent, there is no particular limitation as long as it can dissolve the compound. As specific examples, water, or alcohols such as methanol, ethanol, propanol, butanol; ethers such as diethyl ether, tetrahydrofuran, dioxane; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone; esters such as ethyl acetate; and organic solvents such as N,N-dimethyl sulfoxide, dimethylformamide, dimethylacetamide or N-methyl-2-pyrrolidone can be used appropriately according to the type of reaction.
[0062] Examples of the imidization method in step (iii) include: i -3) is heated to form a solution of a compound represented by formula (d) i The catalytic imidization method in which a catalyst is added to a solution of the compound represented by -3) is preferably the catalytic imidization method from the viewpoint of ease of synthesis.
[0063] The above catalytic imidization can be carried out in the following manner: i A basic catalyst and an acid anhydride are added to a solution of the compound represented by formula (d-3), and the reaction is preferably carried out at 0 to 120°C, more preferably at 0 to 100°C. The amount of the basic catalyst is i The amount of the acid anhydride is preferably 0.5 to 30 times, more preferably 2 to 20 times the amount of the amic acid group of the compound represented by the formula (d i -3) is preferably 1 to 50 times, more preferably 1 to 30 times the amount of the amic acid group of the compound shown in the formula (I)-3). As the basic catalyst, pyridine, triethylamine, trimethylamine, tributylamine or trioctylamine can be listed, among which pyridine has a moderate alkalinity for the reaction to proceed, so it is preferred. As the acid anhydride, acetic anhydride, trimellitic anhydride or pyromellitic anhydride can be listed, among which, when acetic anhydride is used, purification after the reaction becomes easy, so it is preferred.
[0064] The diamine of the present invention can be used as a raw material for a polymer constituting a liquid crystal alignment film. Examples of the polymer include: a polymer (P) selected from the group consisting of: A -1)~(d A -6) and at least one of the group consisting of a polyimide precursor obtained from a diamine component of a diamine (0) represented by any formula and a polyimide which is an imidation product of the polyimide precursor.
[0065] (Polymer (P))
[0066] The polymer (P) of the present invention is a polyimide obtained by using a diamine component containing the above diamine (0) or a polyimide which is an imidation product of the polyimide precursor. Here, the polyimide precursor is a polymer such as polyamic acid and polyamic acid ester which can obtain a polyimide by imidization.
[0067] The polyamic acid (P') as the polyimide precursor of the polymer (P) can be obtained by polymerization reaction of a diamine component containing the diamine (0) and a tetracarboxylic acid component. The diamine (0) may be used alone or in combination of two or more.
[0068] The usage-amount of diamine (0) is preferably 5 mol% or more, more preferably 10 mol% or more, and further preferably 20 mol% or more, based on the total diamine components.
[0069] The diamine component used to produce the polyamic acid (P') may contain a diamine other than diamine (0) (hereinafter, also referred to as other diamines). When other diamines are used in addition to the diamine (0), the amount of diamine (0) used relative to the diamine component is preferably 90 mol% or less, more preferably 80 mol% or less.
[0070] Examples of other diamines are listed below, but are not limited to these. The above other diamines can be used alone or in combination of two or more. p-phenylenediamine, 2,3,5,6-tetramethyl-p-phenylenediamine, 2,5-dimethyl-p-phenylenediamine, m-phenylenediamine, 2,4-dimethyl-m-phenylenediamine, 2,5-diaminotoluene, 2,6-diaminotoluene, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dimethoxy-4,4'-diaminobiphenyl, 3,3'-dihydroxy-4,4'-diamino biphenyl, 2,2'-difluoro-4,4'-diaminobiphenyl, 3,3'-difluoro-4,4'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 3,3'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 3,4'-diaminobiphenyl, 4,4'-diaminobiphenyl, 3,3'-diaminobiphenyl, 2,2'-diaminobiphenyl, 2,3'-diaminobiphenyl, the following formula (d AL ) represented by a diamine (preferably the following formula (d AL -1)~(d AL1,7-bis(4-aminophenoxy)heptane, 1,7-bis(3-aminophenoxy)heptane, 1,8-bis(4-aminophenoxy)octane, 1,8-bis(3-aminophenoxy)octane, 1,9-bis(4-aminophenoxy)nonane, 1,9-bis(3-aminophenoxy)nonane, 1,10-bis(4-aminophenoxy)decane, 1,10-bis(3-aminophenoxy)decane, 1,11-bis(4-aminophenoxy)undecane, 1,11-bis(3-aminophenoxy)undecane, 1,12-bis(4-aminophenoxy)dodecane, 1,12-bis(3-aminophenoxy)dodecane, 1,2-bis(6-amino-2-naphthyloxy)ethane , 1,2-bis(6-amino-2-naphthyl)ethane or 6-[2-(4-aminophenoxy)ethoxy]-2-naphthylamine), 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)diphenyl ether, 1,4-bis[4-(4-aminophenoxy)phenoxy]benzene, 1,4-phenylenebis(4-aminobenzoate), 1,4-phenylenebis(3-aminobenzoate), 1,3-phenylenebis(4-aminobenzoate), 1,3-phenylenebis(3-aminobenzoate) , bis(4-aminophenyl)terephthalate, bis(3-aminophenyl)terephthalate, bis(4-aminophenyl)isophthalate, bis(3-aminophenyl)isophthalate; diamines having a tetracarboxylic acid diimide structure other than specific diamines such as N,N'-bis(4-aminophenyl)-cyclobutane-(1,2,3,4)-tetracarboxylic acid diimide, N,N'-bis(4-aminophenyl)-1,3-dimethylcyclobutane-(1,2,3,4)-tetracarboxylic acid diimide, N,N'-bis(2,2'-bis(trifluoromethyl)-4'-amino-1,1'-biphenyl-4-yl)-cyclobutane-(1,2,3,4)-tetracarboxylic acid diimide; 4,4'-diaminoazobenzene or diaminoazobenzene diamines having photo-aligning groups such as phenylvinyl acetate; diamines having photopolymerizable groups at the ends such as 2-(2,4-diaminophenoxy)ethyl methacrylate or 2,4-diamino-N,N-diallylaniline; diamines having free radical polymerization initiator functions such as 1-(4-(2-(2,4-diaminophenoxy)ethoxy)phenyl)-2-hydroxy-2-methylacetone and 2-(4-(2-hydroxy-2-methylpropionyl)phenoxy)ethyl 3,5-diaminobenzoic acid; diamines having amide bonds such as 4,4'-diaminobenzanilide, and diamines having urea bonds such as 1,3-bis(4-aminophenyl)urea, 1,3-bis(4-aminobenzyl)urea, and 1,3-bis(4-aminophenethyl)urea;3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2-bis(3-aminophenyl)hexafluoropropane, 2,2-bis(3-amino-4-methylphenyl)hexafluoropropane, 2,2-bis(4-aminophenyl)propane, 2,2-bis(3-aminophenyl)propane, 2,2-bis(3-amino-4-methylphenyl)propane, 4,4'-diaminobenzophenone, 1,4-bis(4-aminobenzyl)benzene; 2,6-diaminopyridine, 3,4-diamino Pyridine, 2,4-diaminopyrimidine, 3,6-diaminocarbazole, N-methyl-3,6-diaminocarbazole, 1,4-bis-(4-aminophenyl)-piperazine, 3,6-diaminoacridine, N-ethyl-3,6-diaminocarbazole, N-phenyl-3,6-diaminocarbazole, N-[3-(1H-imidazol-1-yl)propyl]3,5-diaminobenzamide, 4-[4-[(4-aminophenoxy)methyl]-4,5-dihydro-4-methyl-2-oxazolyl]-aniline, or a diamine represented by the following formula (z-1) to formula (z-13), or a heterocyclic diamine such as 4,4'-diaminodiphenylamine, 4,4'-diaminodiphenyl-N-methylamine, N,N'-bis(4-aminophenyl)-biphenyl diamines having a diphenylamine structure, such as 1,4-diaminobenzidine, N,N'-bis(4-aminophenyl)-N,N'-dimethylbenzidine or N,N'-bis(4-aminophenyl)-N,N'-dimethyl-1,4-phenylenediamine, and having at least one nitrogen-containing structure selected from the group consisting of a nitrogen-containing heterocyclic ring, a secondary amino group and a tertiary amino group (hereinafter also referred to as a specific nitrogen-containing structure) (wherein the molecule does not have an amino group bonded to a protective group that is released and substituted with a hydrogen atom by heating); 2,4-diaminophenol, 3,5-diaminophenol, 3,5-diaminobenzyl alcohol, 2,4-diaminobenzyl alcohol, 4,6-diaminoresorcinol, 4,4'-diamino-3,3'-dihydroxybiphenyl; 2, Diamines having a carboxyl group, such as 4-diaminobenzoic acid, 2,5-diaminobenzoic acid, 3,5-diaminobenzoic acid, 4,4'-diaminobiphenyl-3-carboxylic acid, 4,4'-diaminodiphenylmethane-3-carboxylic acid, 1,2-bis(4-aminophenyl)ethane-3-carboxylic acid, 4,4'-diaminobiphenyl-3,3'-dicarboxylic acid, 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid, 3,3'-diaminobiphenyl-4,4'-dicarboxylic acid, 3,3'-diaminobiphenyl-2,4'-dicarboxylic acid, 4,4'-diaminodiphenylmethane-3,3'-dicarboxylic acid, 1,2-bis(4-aminophenyl)ethane-3,3'-dicarboxylic acid, and 4,4'-diaminodiphenyl ether-3,3'-dicarboxylic acid;4-(2-(methylamino)ethyl)aniline, 4-(2-aminoethyl)aniline, 1-(4-aminophenyl)-1,3,3-trimethyl-1H-indane-5-amine, 1-(4-aminophenyl)-2,3-dihydro-1,3,3-trimethyl-1H-indane-6-amine; diamines having a group "-N(D)-" (D represents a protective group that is detached and substituted by a hydrogen atom by heating, preferably a carbamate protective group, more preferably a tert-butyloxycarbonyl group. However, the above-mentioned specific diamines are not included), cholesteryloxy-3,5-diaminobenzene, cholesteryloxy-3,5-diaminobenzene, cholesteryloxy-2,4-diaminobenzene, cholesteryl 3,5-diaminobenzoate ester, 3,5-diaminobenzoic acid cholesteryl ester, 3,5-diaminobenzoic acid lanosteryl ester and 3,6-bis(4-aminobenzoyloxy)cholestane, diamines represented by the following formulas (V-1) to (V-2); diamines having a siloxane bond such as 1,3-bis(3-aminopropyl)-tetramethyldisiloxane; meta-xylylenediamine, 1,3-propylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, 1,3-bis(aminomethyl)cyclohexane, 1,4-diaminocyclohexane, 4,4'-methylenebis(cyclohexylamine), and diamines in which two amino groups are bonded to a group represented by any of the formulas (Y-1) to (Y-167) described in WO2018 / 117239, etc.;
[0071]
[0072] (Ar1 and Ar 1’ Each independently represents a benzene ring, a biphenyl structure or a naphthalene ring, and one or more hydrogen atoms on the benzene ring, the biphenyl structure or the naphthalene ring are optionally substituted by a monovalent group. 1’ Each independently represents a single bond, -O-, -C(=O)-, -C(=O)-O-, or -O-C(=O)-. A represents -CH2-, an alkylene group having 2 to 12 carbon atoms, or a divalent organic group in which at least any of -O-, -C(=O)-O-, and -O-C(=O)- is inserted between carbon-carbon bonds of the alkylene group. Any hydrogen atom possessed by A may be substituted with a halogen atom.
[0073] One or more hydrogen atoms on the benzene ring, biphenyl structure or naphthalene ring are optionally substituted by a monovalent group, and examples of the monovalent group include: a halogen atom, an alkyl group having 1 to 3 carbon atoms, an alkenyl group having 2 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, a fluoroalkyl group having 1 to 3 carbon atoms, a fluoroalkenyl group having 2 to 3 carbon atoms, a fluoroalkoxy group having 1 to 3 carbon atoms, an alkoxycarbonyl group having 2 to 3 carbon atoms, a cyano group, a nitro group, etc.)
[0074]
[0075] (In formula (d AL -6), the total of m1, m2 and n is 3 to 12. AL -8), the total of m1, m2 and n is 3 to 12.
[0076]
[0077]
[0078] In the above formula (V-1), m and n are each independently an integer of 0 to 3, and satisfy 1≤m+n≤4. j is an integer of 0 or 1. 1 Indicates - (CH2) a -(a is an integer of 1 to 15), -CONH-, -NHCO-, -CO-N(CH3)-, -NH-, -O-, -CH2O-, -CH2-OCO-, -COO- or -OCO-. 1 represents a monovalent group such as a fluorine atom, an alkyl group having 1 to 10 carbon atoms and containing a fluorine atom, an alkoxy group having 1 to 10 carbon atoms, an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, and an alkoxyalkyl group having 2 to 10 carbon atoms. 2 represents -O-, -CH2O-, -CH2-OCO-, -COO-, or -OCO-. 1 , R 1 , each independently has the above definition.
[0079] When other diamines are used in addition to the diamine (0), the amount of the other diamines used is preferably 10 to 90 mol %, more preferably 20 to 80 mol %, based on the total amount of the diamine components used.
[0080] As for the above-mentioned other diamines, various diamines can be used according to the purpose. For example, from the viewpoint of improving the voltage holding characteristics when used as a liquid crystal alignment film, it is preferred to select at least one diamine from the group consisting of the following diamines: diamines having at least one group selected from the group consisting of a urea bond, an amide bond, a carboxyl group and a hydroxyl group in the molecule, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether and the above-mentioned diamines having a specific nitrogen atom-containing structure.
[0081] The usage-amount of the said other diamine is preferably 10-90 mol% with respect to the whole diamine component for manufacturing a polymer (P), More preferably, it is 20-80 mol%.
[0082] (Tetracarboxylic acid component)
[0083] When producing the polyamic acid (P′), the tetracarboxylic acid component to be reacted with the diamine component may be not only tetracarboxylic dianhydride but also derivatives of tetracarboxylic dianhydride such as tetracarboxylic acid, tetracarboxylic acid dihalide, tetracarboxylic acid dialkyl ester or tetracarboxylic acid dialkyl ester dihalide.
[0084] The above-mentioned tetracarboxylic dianhydride or its derivatives can be listed as: non-cyclic aliphatic tetracarboxylic dianhydride, alicyclic tetracarboxylic dianhydride, aromatic tetracarboxylic dianhydride, or their derivatives. Among them, it is more preferred to include tetracarboxylic dianhydride or their derivatives having at least one partial structure selected from the group consisting of a benzene ring, a cyclobutane ring, a cyclopentane ring, and a cyclohexane ring. In particular, it is further preferred to include tetracarboxylic dianhydride or their derivatives having at least one structure selected from the group consisting of a cyclobutane ring, a cyclopentane ring, and a cyclohexane ring.
[0085] Here, the non-cyclic aliphatic tetracarboxylic dianhydride is an acid dianhydride obtained by intramolecular dehydration of four carboxyl groups bonded to a chain hydrocarbon structure. However, it is not necessary to be composed of only a chain hydrocarbon structure, and may have an alicyclic structure or an aromatic ring structure in part.
[0086] Alicyclic tetracarboxylic dianhydride is an acid dianhydride obtained by intramolecular dehydration of four carboxyl groups including at least one carboxyl group bonded to an alicyclic structure. Among them, none of these four carboxyl groups is bonded to an aromatic ring. In addition, it is not necessary to be composed only of an alicyclic structure, and a part of it may also have a chain hydrocarbon structure or an aromatic ring structure.
[0087] Aromatic tetracarboxylic dianhydride is an acid dianhydride obtained by intramolecular dehydration of four carboxyl groups including at least one carboxyl group bonded to an aromatic ring. It does not need to be composed of only an aromatic ring structure, and may have a chain hydrocarbon structure or an alicyclic structure in part.
[0088] As a tetracarboxylic acid component which can be used for manufacturing the said polyamic acid (P'), it is preferable to contain the following tetracarboxylic dianhydride or its derivative (in this invention, these are also collectively referred to as a specific tetracarboxylic acid derivative).
[0089] Non-cyclic aliphatic tetracarboxylic dianhydrides such as 1,2,3,4-butanetetracarboxylic dianhydride; 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-dichloro-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-difluoro-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-bis(trifluoromethyl)-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1 , 2,3,4-cyclopentanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 3,3',4,4'-dicyclohexyltetracarboxylic dianhydride, 2,3,5-tricarboxycyclopentylacetic dianhydride, 4-(2,5-dioxotetrahydrofuran-3-yl)tetrahydronaphthalene-1,2-dicarboxylic anhydride, 5-(2,5-dioxotetrahydrofuran-3-yl)-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 5-(2,5-dioxotetrahydrofuran-3-yl)-8-methyl-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3 alicyclic tetracarboxylic dianhydrides such as bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic dianhydride, 2,4,6,8-tetracarboxybicyclo[3.3.0]octane-2:4,6:8-dianhydride; pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 3,3' Aromatic tetracarboxylic dianhydrides such as 4,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)-2,2-diphenylpropane dianhydride, ethylene glycol ditrimellitic anhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 4,4'-carbonyldiphthalic anhydride, 4,4'-(1,4-phenylenedioxy)bis(phthalic anhydride) or 4,4'-(1,4-phenylenedimethylene)bis(phthalic anhydride); and tetracarboxylic dianhydrides described in Japanese Patent Application Publication No. 2010-97188.
[0090] Preferred examples of the specific tetracarboxylic acid derivatives include 1,2,3,4-butanetetracarboxylic dianhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-difluoro-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-bis(trifluoromethyl)-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 3,3',4,4'-dicyclohexyltetracarboxylic dianhydride, 2,3,5-tricarboxycyclopentylacetic dianhydride, 5-(2,5-dioxotetrahydro furan-3-yl)-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 5-(2,5-dioxotetrahydrofuran-3-yl)-8-methyl-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 2,4,6,8-tetracarboxybicyclo[3.3.0]octane-2:4,6:8-dianhydride, pyromellitic dianhydride , 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 3,3',4,4'-diphenylethertetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, or derivatives thereof.
[0091] The usage ratio of the said specific tetracarboxylic acid derivative is preferably 10 mol% or more, more preferably 20 mol% or more, and further preferably 50 mol% or more, based on the whole tetracarboxylic acid components used.
[0092] (Liquid Crystal Alignment Agent)
[0093] The liquid crystal aligning agent of the present invention is a liquid composition in which the polymer (P) and other components used as needed are preferably dispersed or dissolved in an appropriate solvent.
[0094] The total content of the polymers contained in the liquid crystal aligning agent of the present invention can also be appropriately changed according to the setting of the thickness of the coating film to be formed. From the perspective of forming a uniform and defect-free coating film, it is preferably 1% by mass or more, and from the perspective of the storage stability of the solution, it is preferably 10% by mass or less. The total content of the polymers is particularly preferably 2 to 8% by mass.
[0095] The content of the polymer (P) used in the present invention is preferably 1 to 100 mass %, more preferably 10 to 100 mass %, particularly preferably 20 to 100 mass %, based on the total amount of the polymers contained in the liquid crystal aligning agent.
[0096] The liquid crystal alignment agent of the present invention may also contain other polymers other than the polymer (P). If specific examples of other polymers are listed, in addition to the above-mentioned polymer (P), polymers selected from the group consisting of the following substances can also be listed: at least one polymer selected from the group consisting of a polyimide precursor obtained by using a diamine component that does not have the above-mentioned specific diamine and a polyimide that is an imide product of the polyimide precursor (also referred to as polymer (B) in the present invention), polysiloxane, polyester, polyamide, polyurea, polyorganosiloxane, cellulose derivative, polyacetal, polystyrene derivative, poly(styrene-maleic anhydride) copolymer, poly(isobutylene-maleic anhydride) copolymer, poly(vinyl ether-maleic anhydride) copolymer, poly(styrene-phenylmaleimide) derivative, poly(meth)acrylate.
[0097] Specific examples of poly(styrene-maleic anhydride) copolymers include SMA1000, SMA2000, SMA3000 (manufactured by Cray Valley), GSM301 (manufactured by Gifu Shellac Manufacturing), etc. Specific examples of poly(isobutylene-maleic anhydride) copolymers include ISOBAM-600 (manufactured by Kuraray). Specific examples of poly(vinyl ether-maleic anhydride) copolymers include Gantrez AN-139 (methyl vinyl ether maleic anhydride resin, manufactured by Ashland).
[0098] Among them, the polymer (B) is more preferred from the viewpoint of maintaining the voltage holding ratio and reducing the afterimage caused by the residual DC.
[0099] The above other polymers may be used alone or in combination of two or more. The content of the other polymers is preferably 90 parts by mass or less, more preferably 10 to 90 parts by mass, and further preferably 20 to 80 parts by mass, relative to 100 parts by mass of the total polymers contained in the liquid crystal aligning agent.
[0100] (Polymer (B))
[0101] The specific examples of the tetracarboxylic acid components used to manufacture the above-mentioned polymer (B) include preferred specific examples, and the same compounds as those exemplified in the polymer (P) can be listed. The tetracarboxylic acid components used to manufacture the polymer (B) more preferably include tetracarboxylic dianhydride or their derivatives having at least one partial structure selected from the group consisting of a benzene ring, a cyclobutane ring, a cyclopentane ring, and a cyclohexane ring, and the above-mentioned specific tetracarboxylic acid derivatives are further preferred, and the above-mentioned specific tetracarboxylic acid derivatives are most preferably used. More preferred specific examples. From the viewpoint of appropriately obtaining the effect of the present invention, the tetracarboxylic acid components used to manufacture the polymer (B) are preferably non-cyclic aliphatic tetracarboxylic dianhydride, alicyclic tetracarboxylic dianhydride or their derivatives.
[0102] Moreover, the usage-amount of the said specific tetracarboxylic acid derivative is preferably 10 mol% or more, more preferably 20 mol% or more, and further preferably 50 mol% or more with respect to the whole tetracarboxylic acid component for producing a polymer (B).
[0103] As the diamine component for obtaining the polymer (B), for example, the diamines exemplified in the above polymer (P) can be cited. Among them, from the viewpoint of improving the liquid crystal orientation, the diamine component for obtaining the polymer (B) preferably includes p-phenylenediamine, 2,3,5,6-tetramethyl-p-phenylenediamine, 2,5-dimethyl-p-phenylenediamine, m-phenylenediamine, 2,4-dimethyl-m-phenylenediamine, 2,5-diaminotoluene, 2,6-diaminotoluene, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dimethoxy-4,4'-diaminobiphenyl , 3,3'-dihydroxy-4,4'-biphenyl, 2,2'-difluoro-4,4'-biphenyl, 3,3'-difluoro-4,4'-biphenyl, 2,2'-bis(trifluoromethyl)-4,4'-biphenyl, 3,3'-bis(trifluoromethyl)-4,4'-biphenyl, 3,4'-biphenyl, 4,4'-biphenyl, 3,3'-biphenyl, 2,2'-biphenyl, 2,3'-biphenyl, the above formula (d AL ) or a diamine having a tetracarboxylic acid diimide structure other than the above-mentioned specific diamine (hereinafter, these are also collectively referred to as diamine (c)). AL A preferred specific example of the diamine represented by ) is the above formula (d AL -1)~(d AL-10), 1,7-bis(4-aminophenoxy)heptane, 1,7-bis(3-aminophenoxy)heptane, 1,8-bis(4-aminophenoxy)octane, 1,8-bis(3-aminophenoxy)octane, 1,9-bis(4-aminophenoxy)nonane, 1,9-bis(3-aminophenoxy)nonane, 1,10-bis(4-aminophenoxy)decane, 1,10-bis(3-aminophenoxy) 1,11-bis(4-aminophenoxy)undecane, 1,11-bis(3-aminophenoxy)undecane, 1,12-bis(4-aminophenoxy)dodecane, 1,12-bis(3-aminophenoxy)dodecane, 1,2-bis(6-amino-2-naphthyl)ethane, 1,2-bis(6-amino-2-naphthyl)ethane or 6-[2-(4-aminophenoxy)ethoxy]-2-naphthylamine. The above diamine components may be used alone or in combination of two or more.
[0104] When the above-mentioned diamine (c) is used, its usage amount is preferably 10 mol% or more, more preferably 20 mol% or more of the total diamine components used to produce the polymer (B). When a diamine other than diamine (c) is used, its usage amount is preferably 90 mol% or less, more preferably 80 mol% or less of the total diamine components used to produce the polymer (B).
[0105] (Manufacture of polyamic acid)
[0106] The manufacture of polyamic acid is carried out by reacting a diamine component with a tetracarboxylic acid component in an organic solvent. As for the use ratio of the tetracarboxylic acid component and the diamine component for the manufacture reaction of polyamic acid, the anhydride group of the tetracarboxylic acid component is preferably 0.5 to 2 equivalents relative to 1 equivalent of the amino group of the diamine component, and more preferably 0.8 to 1.2 equivalents. As in the usual polycondensation reaction, the closer the equivalent of the anhydride group of the tetracarboxylic acid component is to 1 equivalent, the greater the molecular weight of the generated polyamic acid.
[0107] The reaction temperature in the manufacture of polyamic acid is preferably -20 to 150°C, more preferably 0 to 100°C. In addition, the reaction time is preferably 0.1 to 24 hours, more preferably 0.5 to 12 hours. The manufacture of polyamic acid can be carried out at any concentration, but the concentration of polyamic acid is preferably 1 to 50% by mass, more preferably 5 to 30% by mass. It is also possible to carry out the reaction at a high concentration in the initial stage and then add a solvent.
[0108] Specific examples of the organic solvent include cyclohexanone, cyclopentanone, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, γ-butyrolactone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and 1,3-dimethyl-2-imidazolidinone. In addition, when the polymer has high solvent solubility, solvents such as methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, propylene glycol monomethyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, diethylene glycol monomethyl ether, or diethylene glycol monoethyl ether can be used.
[0109] (Production of polyamic acid ester)
[0110] Polyamic acid ester can be obtained by, for example, a known method such as [I] a method of reacting a polyamic acid obtained by the above method with an esterifying agent, [II] a method of reacting a tetracarboxylic acid diester with a diamine, or [III] a method of reacting a tetracarboxylic acid diester dihalide with a diamine.
[0111] (Manufacture of polyimide)
[0112] As for polyimide, polyimide can be obtained by ring-closing (imidizing) a polyimide precursor such as the above-mentioned polyamic acid or polyamic acid ester. It should be noted that the imidization rate mentioned in this specification refers to the proportion of the imide group in the total amount of the imide group and the carboxyl group (or its derivative) derived from tetracarboxylic dianhydride or its derivative. The imidization rate does not necessarily have to be 100%, and can be arbitrarily adjusted according to the use and purpose.
[0113] Examples of a method for imidating a polyimide precursor include thermal imidization in which a solution of a polyimide precursor is heated while it is maintained, and catalytic imidization in which a catalyst is added to a solution of a polyimide precursor.
[0114] The temperature when thermally imidizing the polyimide precursor in a solution is preferably 100 to 400° C., more preferably 120 to 250° C., and the imidization reaction is preferably performed while removing water generated by the imidization reaction to the outside of the system.
[0115] The catalytic imidization of the polyimide precursor can be carried out as follows: add a basic catalyst and an acid anhydride to a solution of the polyimide precursor, preferably stirring at -20 to 250°C, more preferably at 0 to 180°C. The amount of the basic catalyst is preferably 0.5 to 30 times the molar amount of the amic acid group, more preferably 2 to 20 times, and the amount of the acid anhydride is preferably 1 to 50 times the molar amount of the amic acid group, more preferably 3 to 30 times. As the basic catalyst, pyridine, triethylamine, trimethylamine, tributylamine or trioctylamine can be listed, among which pyridine has a moderate alkalinity for the progress of the reaction, so it is preferred. As the acid anhydride, acetic anhydride, trimellitic anhydride or pyromellitic anhydride can be listed, among which, when acetic anhydride is used, purification after the reaction becomes easy, so it is preferred. The imidization rate based on catalytic imidization can be controlled by adjusting the amount of catalyst, reaction temperature and reaction time.
[0116] In the case of recovering the generated polyimide precursor or polyimide from the reaction solution of the polyimide precursor or polyimide, it is sufficient to put the reaction solution into a solvent to precipitate it. As solvents for precipitation, methanol, ethanol, isopropanol, acetone, hexane, butyl cellosolve, heptane, methyl ethyl ketone, methyl isobutyl ketone, toluene, benzene, water, etc. can be listed. The polymer precipitated by being put into the solvent can be filtered and recovered, and then dried at room temperature or heated under normal pressure or reduced pressure. In addition, when the recovered polymer is repeatedly dissolved in an organic solvent and reprecipitated and recovered 2 to 10 times, the impurities in the polymer can be reduced. As solvents at this time, for example, alcohols, ketones or hydrocarbons can be listed. When three or more solvents selected from these are used, the efficiency of purification is further improved, so it is preferred.
[0117] When the polyimide precursor and polyimide in the present invention are produced, a suitable end-capping agent may be used together with a tetracarboxylic acid component including tetracarboxylic dianhydride or a derivative thereof and a diamine component including the above-mentioned diamine to produce an end-capped polymer. The end-capped polymer has the effect of increasing the film hardness of the oriented film obtained from the coating film and improving the adhesion between the sealant and the oriented film.
[0118] Examples of the terminal of the polyimide precursor or polyimide in the present invention include amino groups, carboxyl groups, acid anhydride groups, or groups derived from the terminal blocking agent described below. The amino groups, carboxyl groups, and acid anhydride groups can be obtained by a common condensation reaction or by blocking with the following terminal blocking agent.
[0119] Examples of the end-capping agent include: anhydrides such as acetic anhydride, maleic anhydride, nadic anhydride, phthalic anhydride, itaconic anhydride, 1,2-cyclohexanedicarboxylic anhydride, 3-hydroxyphthalic anhydride, trimellitic anhydride, 3-(3-trimethoxysilyl)propyl-3,4-dihydrofuran-2,5-dione, 4,5,6,7-tetrafluoroisobenzofuran-1,3-dione, and 4-ethynylphthalic anhydride; dicarbonic acid diester compounds such as di-tert-butyl dicarbonate and diallyl dicarbonate; acryloyl chloride, methyl Chlorocarbonyl compounds such as acryloyl chloride and nicotinoyl chloride; monoamine compounds such as aniline, 2-aminophenol, 3-aminophenol, 4-aminosalicylic acid, 5-aminosalicylic acid, 6-aminosalicylic acid, 2-aminobenzoic acid, 3-aminobenzoic acid, 4-aminobenzoic acid, cyclohexylamine, n-butylamine, n-pentylamine, n-hexylamine, n-heptylamine, n-octylamine; isocyanates with unsaturated bonds such as ethyl isocyanate, phenyl isocyanate, naphthyl isocyanate or 2-acryloyloxyethyl isocyanate, 2-methacryloyloxyethyl isocyanate, etc.
[0120] The usage ratio of the terminal blocking agent is preferably 0.01 to 20 parts by mole, more preferably 0.01 to 10 parts by mole, based on 100 parts by mole of the total diamine component used.
[0121] The polyimide precursor and the polyimide preferably have a weight average molecular weight (Mw) in terms of polystyrene measured by gel permeation chromatography (GPC) of 1,000 to 500,000, and more preferably 2,000 to 300,000. In addition, the molecular weight distribution (Mw / Mn) represented by the ratio of Mw to the number average molecular weight (Mn) in terms of polystyrene measured by GPC is preferably 15 or less, and more preferably 10 or less. By being within this molecular weight range, good orientation of the liquid crystal display element can be ensured.
[0122] The organic solvent contained in the liquid crystal aligning agent of the present invention is not particularly limited as long as it uniformly dissolves the polymer (P) and other polymers added as needed. For example, N, N-dimethylformamide, N, N-dimethylacetamide, N, N-dimethyllactamide, N, N-dimethylpropionamide, tetramethylurea, N, N-diethylformamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethyl sulfoxide, γ-butyrolactone, γ-valerolactone, 1, 3-dimethyl-2-imidazolidinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, 3-methoxy-N, N-dimethylpropionamide , 3-butoxy-N, N-dimethylpropionamide, N-n-propyl-2-pyrrolidone, N-isopropyl-2-pyrrolidone, N-n-butyl-2-pyrrolidone, N-tert-butyl-2-pyrrolidone, N-n-pentyl-2-pyrrolidone, N-methoxypropyl-2-pyrrolidone, N-ethoxyethyl-2-pyrrolidone, N-methoxybutyl-2-pyrrolidone, N-cyclohexyl-2-pyrrolidone (these are also collectively referred to as good solvents), etc. Among them, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 3-methoxy-N, N-dimethylpropionamide, 3-butoxy-N, N-dimethylpropionamide or γ-butyrolactone is preferred. The content of the good solvent is preferably 20 to 99% by mass of the total solvent contained in the liquid crystal aligning agent, more preferably 20 to 90% by mass, and particularly preferably 30 to 80% by mass.
[0123] In addition, the organic solvent contained in the liquid crystal aligning agent is preferably used in addition to the above-mentioned solvent and a mixed solvent of a solvent (also referred to as a poor solvent) that improves the coating property and surface smoothness of the coating film when the liquid crystal aligning agent is applied. Specific examples of poor solvents are described below, but are not limited thereto. The content of the poor solvent is preferably 1 to 80% by mass of the entire solvent contained in the liquid crystal aligning agent, more preferably 10 to 80% by mass, and particularly preferably 20 to 70% by mass. The type and content of the poor solvent are appropriately selected according to the coating device, coating conditions, coating environment, etc. of the liquid crystal aligning agent.
[0124] Examples of the poor solvent include diisopropyl ether, diisobutyl ether, diisobutyl carbinol (2,6-dimethyl-4-heptanol), ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, 4-hydroxy-4-methyl-2-pentanone, diethylene glycol methyl ethyl ether, diethylene glycol dibutyl ether, 3-ethoxybutyl acetate, 1-methylpentyl acetate, 2-ethylbutyl acetate, 2-ethylhexyl acetate, ethylene glycol monoacetate, ethylene glycol diacetate, propylene carbonate, ethylene carbonate, ethylene glycol monobutyl ether, ethylene glycol monoisopentyl ether, ethylene glycol monohexyl ether, propylene glycol monomethyl ether, propylene glycol monobutyl ether, 1-(2-butoxyethoxy)-2-propanol, 2-(2-butoxyethoxy)-1-propanol, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol dimethyl ether, ethylene glycol monobutyl ether acetate, diethylene glycol monopropyl ether, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, 2-(2-ethoxyethoxy)ethyl acetate, diethylene glycol acetate, propylene glycol diacetate, n-butyl acetate, propylene glycol monoethyl acetate, cyclohexyl acetate, 4-methyl-2-pentyl acetate, 3-methoxypropionic acid methyl ester, 3-ethoxypropionic acid ethyl ester, 3-methoxypropionic acid ethyl ester, 3-methoxypropionic acid propyl ester, 3-methoxypropionic acid butyl ester, n-butyl lactate, isopentyl lactate, diethylene glycol monoethyl ether, diisobutyl ketone (2,6-dimethyl-4-heptanone), etc.
[0125] Among them, diisobutylcarbinol, propylene glycol monobutyl ether, propylene glycol diacetate, diethylene glycol diethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol dimethyl ether, 4-hydroxy-4-methyl-2-pentanone, ethylene glycol monobutyl ether, ethylene glycol monobutyl ether acetate or diisobutyl ketone is preferred.
[0126] Preferred combinations of good solvents and poor solvents include: N-methyl-2-pyrrolidone and ethylene glycol monobutyl ether; N-methyl-2-pyrrolidone, γ-butyrolactone and ethylene glycol monobutyl ether; N-methyl-2-pyrrolidone, γ-butyrolactone and propylene glycol monobutyl ether; N-ethyl-2-pyrrolidone and propylene glycol monobutyl ether; N-ethyl-2-pyrrolidone and 4-hydroxy-4-methyl-2-pentanone; N-ethyl-2-pyrrolidone and propylene glycol diacetate; N,N-dimethyl lactamide and diisobutyl ketone; N-methyl-2-pyrrolidone and ethyl 3-ethoxypropionate; N-ethyl-2-pyrrolidone and ethyl 3-ethoxypropionate; N-methyl-2-pyrrolidone, ethyl 3-ethoxypropionate and and dipropylene glycol monomethyl ether; N-ethyl-2-pyrrolidone, ethyl 3-ethoxypropionate and propylene glycol monobutyl ether; N-methyl-2-pyrrolidone, ethyl 3-ethoxypropionate and diethylene glycol monopropyl ether; N-ethyl-2-pyrrolidone, ethyl 3-ethoxypropionate and diethylene glycol monopropyl ether; N-methyl-2-pyrrolidone and ethylene glycol monobutyl ether acetate; N-ethyl-2-pyrrolidone and dipropylene glycol dimethyl ether; N,N-dimethyl lactamide and ethylene glycol monobutyl ether; N,N-dimethyl lactamide and propylene glycol diacetate; N-ethyl-2-pyrrolidone and diethylene glycol diethyl ether; N-ethyl-2-pyrrolidone, diethylene glycol monoethyl ether and butyl cellosolve acetate; N-methyl-2-pyrrolidone Ketone, diethylene glycol monomethyl ether and butyl cellosolve acetate; N,N-dimethyl lactamide and diethylene glycol diethyl ether; N-methyl-2-pyrrolidone, gamma-butyrolactone, 4-hydroxy-4-methyl-2-pentanone and diethylene glycol diethyl ether; N-ethyl-2-pyrrolidone, N-methyl-2-pyrrolidone and 4-hydroxy-4-methyl-2-pentanone; N-ethyl-2-pyrrolidone, 4-hydroxy-4-methyl-2-pentanone and propylene glycol monobutyl ether; N-methyl-2-pyrrolidone, 4-hydroxy-4-methyl-2-pentanone and diisobutyl ketone; N-methyl-2-pyrrolidone, 4-hydroxy-4-methyl-2-pentanone and dipropylene glycol monomethyl ether; N-methyl-2-pyrrolidone, 4-hydroxy-4 N-methyl-2-pentanone and propylene glycol monobutyl ether; N-methyl-2-pyrrolidone, 4-hydroxy-4-methyl-2-pentanone and propylene glycol diacetate; N-ethyl-2-pyrrolidone, 4-hydroxy-4-methyl-2-pentanone and dipropylene glycol dimethyl ether; γ-butyrolactone, 4-hydroxy-4-methyl-2-pentanone and diisobutyl ketone; γ-butyrolactone, 4-hydroxy-4-methyl-2-pentanone and propylene glycol diacetate; N-methyl-2-pyrrolidone, γ-butyrolactone, propylene glycol monobutyl ether and diisobutyl ketone; N-methyl-2-pyrrolidone, γ-butyrolactone, propylene glycol monobutyl ether and diisopropyl ether; N-methyl-2-pyrrolidone, γ-butyrolactone, propylene glycol monobutyl ether and diisobutyl carbinol;N-methyl-2-pyrrolidone, gamma-butyrolactone and dipropylene glycol dimethyl ether; N-methyl-2-pyrrolidone, propylene glycol monobutyl ether and dipropylene glycol dimethyl ether; N-ethyl-2-pyrrolidone, propylene glycol monobutyl ether and dipropylene glycol monomethyl ether; N-ethyl-2-pyrrolidone, diethylene glycol diethyl ether and dipropylene glycol monomethyl ether; N-ethyl-2-pyrrolidone, propylene glycol monobutyl ether and propylene glycol diacetate; N-ethyl-2-pyrrolidone, propylene glycol monobutyl ether and diisobutyl ketone; N-ethyl-2-pyrrolidone, gamma-butyrolactone and diisobutyl ketone; N-ethyl-2-pyrrolidone, N,N-dimethyl Lactamide and diisobutyl ketone; N-methyl-2-pyrrolidone, ethylene glycol monobutyl ether and ethylene glycol monobutyl ether acetate; γ-butyrolactone, ethylene glycol monobutyl ether acetate and dipropylene glycol dimethyl ether; N-ethyl-2-pyrrolidone, ethylene glycol monobutyl ether acetate and propylene glycol dimethyl ether; N-methyl-2-pyrrolidone, 4-methyl-2-pentyl acetate and ethylene glycol monobutyl ether; N-ethyl-2-pyrrolidone, cyclohexyl acetate and 4-hydroxy-4-methyl-2-pentanone; cyclohexanone and propylene glycol monomethyl ether; cyclopentanone and propylene glycol monomethyl ether; N-methyl-2-pyrrolidone, cyclohexanone and propylene glycol monomethyl ether, etc.;
[0127] (additive)
[0128] The liquid crystal alignment agent of the present invention may contain other components (hereinafter referred to as additive components) in addition to the above-mentioned polymer (P), the above-mentioned other polymers and the above-mentioned organic solvent. As the above-mentioned additive components, for example, at least one cross-linking compound selected from the group consisting of a cross-linking compound (c-1) having the following substituents and a cross-linking compound (c-2) having a polymerizable unsaturated group; functional silane compounds; metal chelate compounds; curing accelerators; surfactants; antioxidants; sensitizers; preservatives; compounds for adjusting the dielectric constant and resistance of the obtained liquid crystal alignment film, compounds for promoting imidization, etc., wherein the substituent is selected from at least one of an oxirane group, an oxetane group, a blocked isocyanate group, an oxazoline group, a cyclocarbonate group, a hydroxyl group and an alkoxy group.
[0129] Preferred specific examples of the crosslinking compounds (c-1) and (c-2) include ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, glycerol diglycidyl ether, dibromoneopentyl glycol diglycidyl ether, 1,3,5,6-tetraglycidyl-2,4-hexanediol, bisphenol A type epoxy resins such as EPIKOTE 828 (manufactured by MITSUBISHI Chemical Co., Ltd.), bisphenol F type epoxy resins such as EPIKOTE 807 (manufactured by MITSUBISHI Chemical Co., Ltd.), hydrogenated bisphenol A type epoxy resins such as YX-8000 (manufactured by MITSUBISHI Chemical Co., Ltd.), YX6954BH30 (manufactured by MITSUBISHI Chemical Co., Ltd.), and bisphenol A type epoxy resins such as EPICOTE 828 (manufactured by MITSUBISHI Chemical Co., Ltd.). Epoxy resins containing biphenyl skeletons, such as EPPN-201 (manufactured by Nippon Kayaku Co., Ltd.), phenol novolac type epoxy resins, such as EOCN-102S (manufactured by Nippon Kayaku Co., Ltd.), (o-, m-, p-) cresol novolac type epoxy resins, such as TEPIC (manufactured by Nissan Chemical Co., Ltd.), alicyclic epoxy resins such as CELLOXIDE2021P (manufactured by Daicel Co., Ltd.), N,N,N',N'-tetraglycidyl tertiary nitrogen atom-containing compounds represented by 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane or N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, compounds having two or more oxirane groups such as tetra(glycidyloxymethyl)methane; compounds having two or more oxetane groups described in paragraphs 0170 to 0175 of WO2011 / 132751; CORONATE AP stable M, CORONATE 2503, 2515, 2507, 2513, 2555, MILLIONATE MS-50 (all manufactured by TOSOH), TAKENATE Compounds having a blocked isocyanate group such as B-830, B-815N, B-820NSU, B-842N, B-846N, B-870N, B-874N, and B-882N (all manufactured by Mitsui Chemicals, Inc.); compounds having an oxazoline group such as 2,2'-bis(2-oxazoline), 2,2'-bis(4-methyl-2-oxazoline), 2,2'-bis(5-methyl-2-oxazoline), 1,2,4-tri(2-oxazolinyl)-benzene, and EPOCROS (manufactured by Nippon Shokubai Co., Ltd.); compounds having a cyclic carbonate group as described in paragraphs 0025 to 0030 and 0032 of WO2011 / 155577;Compounds having hydroxyl groups or alkoxy groups, such as N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide, 2,2-bis(4-hydroxy-3,5-dihydroxymethylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethoxyphenyl)propane, and 2,2-bis(4-hydroxy-3,5-dihydroxymethylphenyl)-1,1,1,3,3,3-hexafluoropropane; compounds represented by glycerol mono(meth)acrylate, glycerol di(meth)acrylate (1,2-, 1,3-type mixture), glycerol tri(meth)acrylate, glycerol 1,3-diglycerol alcohol di(meth)acrylate, pentaerythritol tri(meth)acrylate, diethylene glycol mono(meth)acrylate, triethylene glycol mono(meth)acrylate, tetraethylene glycol mono(meth)acrylate, pentaethylene glycol mono(meth)acrylate, and hexaethylene glycol mono(meth)acrylate. ;
[0130] The content of the crosslinking compounds (c-1) and (c-2) contained in the liquid crystal aligning agent of the present invention is preferably 0.1 to 30 parts by mass, more preferably 0.1 to 20 parts by mass, and further preferably 5 to 20 parts by mass, based on 100 parts by mass of the polymer component contained in the liquid crystal aligning agent.
[0131] Examples of the compound for adjusting the dielectric constant and the resistance include monoamines having an aromatic heterocyclic ring containing a nitrogen atom, such as 3-aminomethylpyridine. The content of the monoamine having an aromatic heterocyclic ring containing a nitrogen atom is preferably 0.1 to 30 parts by mass, more preferably 0.1 to 20 parts by mass, based on 100 parts by mass of the polymer component contained in the liquid crystal aligning agent.
[0132] Preferred specific examples of the functional silane compound include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyldiethoxymethylsilane, 2-aminopropyltrimethoxysilane, 2-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-ureidopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, tris(3-trimethoxysilylpropyl)isocyanurate, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, etc. The content of the functional silane compound is preferably 0.1 to 30 parts by mass, more preferably 0.1 to 20 parts by mass, relative to 100 parts by mass of the polymer component contained in the liquid crystal aligning agent.
[0133] As the compound for promoting imidization, a compound having a basic site (e.g., a primary amino group, an aliphatic heterocycle (e.g., a pyrrolidine skeleton), an aromatic heterocycle (e.g., an imidazole ring, an indole ring), or a guanidine group, etc.) is preferred (but excluding the cross-linking compound and the adhesion aid); or a compound that generates the above-mentioned basic site when calcined. More preferred are compounds that generate the above-mentioned basic site when calcined. If preferred specific examples are listed, amino acids in which part or all of the basic sites of amino acids are protected can be listed. As the protecting group of the basic site of the above-mentioned amino acid, carbamate-based protecting groups such as Boc group can be listed. Specific examples of the above-mentioned amino acids include: glycine, alanine, cysteine, methionine, asparagine, glutamic acid, valine, leucine, phenylalanine, tyrosine, tryptophan, proline, hydroxyproline, arginine, histidine, lysine, and ornithine. If more preferred specific examples of compounds for promoting imidization are listed, N-α-(9-fluorenylmethoxycarbonyl)-N-τ-(tert-butyloxycarbonyl)-L-histidine can be listed. The content of the compound for promoting the imidization contained in the liquid crystal aligning agent of the present invention is preferably 0.1 to 30 parts by mass, more preferably 0.1 to 20 parts by mass, and further preferably 5 to 20 parts by mass relative to 100 parts by mass of the polymer component contained in the liquid crystal aligning agent.
[0134] The solid content concentration in the liquid crystal aligning agent (the ratio of the total mass of components other than the solvent of the liquid crystal aligning agent to the total mass of the liquid crystal aligning agent) is appropriately selected in consideration of viscosity, volatility, etc., and is preferably 1 to 10 mass %.
[0135] The range of particularly preferred solid content concentration varies depending on the method used when the liquid crystal alignment agent is applied to the substrate. For example, in the case of using a spin coating method, the solid content concentration is particularly preferably 1.5 to 4.5% by mass. In the case of a printing method, it is particularly preferred to set the solid content concentration to 3 to 9% by mass, thereby setting the solution viscosity to 12 to 50 mPa·s. In the case of an inkjet method, it is particularly preferred to set the solid content concentration to 1 to 5% by mass, thereby setting the solution viscosity to 3 to 15 mPa·s. The temperature when preparing the polymer composition is preferably 10 to 50°C, more preferably 20 to 30°C.
[0136] (Liquid crystal alignment film and liquid crystal display element)
[0137] The liquid crystal display element of the present invention has a liquid crystal alignment film formed by using the above-mentioned liquid crystal alignment agent. The operation mode of the liquid crystal display element is not particularly limited, for example, it can be applied to various operation modes such as TN type, STN (Super Twisted Nematic) type, vertical alignment type (including VA-MVA (Multi-domain Vertical Alignment: Multi-domain Vertical Alignment) type, VA-PVA (Patterned Vertical Alignment: Image Vertical Alignment) type, etc.), in-plane switching type (IPS type, FFS type), optically compensated bending type (OCB: Optically Compensated Birefringence type).
[0138] The liquid crystal display element of the present invention can be manufactured, for example, by a method comprising the following steps (1) to (4); a method comprising steps (1) to (2) and (4); a method comprising steps (1) to (3), (4-2) and (4-4); or a method comprising steps (1) to (3), (4-3) and (4-4).
[0139] <Step (1): Step of applying a liquid crystal aligning agent onto a substrate>
[0140] The step (1) is a step of applying a liquid crystal aligning agent onto a substrate. Specific examples of the step (1) are as follows.
[0141] For example, by a suitable coating method such as a roller coater method, a spin coating method, a printing method, an inkjet method, etc., the liquid crystal alignment agent is applied to one side of a substrate provided with a patterned transparent conductive film. Here, as the material of the substrate, there is no particular limitation as long as it is a substrate with high transparency, and plastics such as acrylic acid, polycarbonate, etc. can also be used together with glass and silicon nitride. In addition, in a reflective liquid crystal display element, if it is a substrate on only one side, an opaque object such as a silicon wafer can also be used, and the electrode in this case can also use a material that reflects light such as aluminum. In addition, in the case of manufacturing an IPS type or FFS type liquid crystal display element, a substrate provided with an electrode composed of a transparent conductive film or a metal film patterned into a comb-shaped shape and an opposing substrate without an electrode are used.
[0142] An IPS substrate, which is a comb-tooth electrode substrate used in an IPS type liquid crystal display element, includes, for example: a substrate; a plurality of linear electrodes formed on the substrate and arranged in a comb-tooth shape; and a liquid crystal alignment film formed on the substrate so as to cover the linear electrodes.
[0143] It should be noted that the FFS substrate, which is a comb-tooth electrode substrate used in an FFS-type liquid crystal display element, has, for example: a substrate; a surface electrode formed on the substrate; an insulating film formed on the surface electrode; a plurality of linear electrodes formed on the insulating film and configured in a comb-tooth shape; and a liquid crystal orientation film formed on the insulating film in a manner covering the linear electrodes.
[0144] As a method of applying a liquid crystal aligning agent to a substrate to form a film, screen printing, offset printing, flexographic printing, an inkjet method, a spray method, etc. are mentioned. Among them, the coating and film-forming method using the inkjet method can be preferably used.
[0145] <Step (2): Step of calcining the applied liquid crystal aligning agent>
[0146] The step (2) is a step of baking the liquid crystal aligning agent applied on the substrate to form a film. Specific examples of the step (2) are as follows.
[0147] After the liquid crystal alignment agent is applied to the substrate in step (1), the solvent can be evaporated by a heating unit such as a heating plate, a hot air circulation oven or an IR (infrared) oven; or thermal imidization of the polyamic acid can be performed. The drying and firing steps after the application of the liquid crystal alignment agent can be selected at any temperature and time, and can also be performed multiple times. The temperature for firing the liquid crystal alignment agent can be, for example, 40 to 180°C. From the perspective of shortening the process, it can be performed at 40 to 150°C. The firing time is not particularly limited, and 1 to 10 minutes or 1 to 5 minutes can be listed. In the case of thermal imidization of polyamic acid, a firing step at 150 to 300°C or 150 to 250°C can be added after the above step. The firing time is not particularly limited, and 5 to 40 minutes or 5 to 30 minutes can be listed.
[0148] If the film thickness of the film-like material after firing is too thin, the reliability of the liquid crystal display element may be reduced, so it is preferably 5 to 300 nm, and more preferably 10 to 200 nm.
[0149] <Step (3): Step of orienting the film obtained in step (2)>
[0150] Step (3) is a step of subjecting the film obtained in step (2) to an orientation treatment, depending on the circumstances. That is, in a horizontally oriented liquid crystal display element such as an IPS mode or an FFS mode, the coating is subjected to an orientation capability imparting treatment. On the other hand, in a vertically oriented liquid crystal display element such as a VA mode or a PSA (Polymer Sustained Alignment: polymer stable alignment) mode, the formed coating can be kept in this state and used as a liquid crystal alignment film, or the coating can be subjected to an orientation capability imparting treatment. As an orientation treatment method for a liquid crystal alignment film, a rubbing orientation treatment method and a photo-orientation treatment method can be listed. As a photo-orientation treatment method, the following method can be listed: irradiating the surface of the above-mentioned film-like object with radiation biased in a certain direction, preferably heating at a temperature of 150 to 250° C., and imparting liquid crystal orientation (also referred to as liquid crystal orientation capability). As radiation, ultraviolet rays or visible light having a wavelength of 100 to 800 nm can be used. Among them, ultraviolet rays having a wavelength of 100 to 400 nm are preferred, and ultraviolet rays having a wavelength of 200 to 400 nm are more preferred.
[0151] The radiation dose is preferably 1 to 10000 mJ / cm 2 , among which 100 to 5000 mJ / cm 2In addition, when irradiating with radiation, the substrate having the film-like material may be heated at 50 to 250° C. to improve the liquid crystal orientation. The liquid crystal orientation film produced in this way can stably align liquid crystal molecules in a certain direction.
[0152] Furthermore, in the above method, the coating film irradiated with polarized radiation or the coating film subjected to rubbing orientation treatment may be subjected to contact treatment using water or a solvent. In addition, the film subjected to the above orientation treatment may be subjected to heat treatment without being subjected to contact treatment. Furthermore, the film subjected to the above contact treatment may be further subjected to heat treatment.
[0153] The solvent used in the above-mentioned contact treatment is not particularly limited as long as it is a solvent that dissolves the decomposition product generated by the film-like material by irradiation with radiation. Specific examples include: water, methanol, ethanol, 2-propanol, acetone, methyl ethyl ketone, 1-methoxy-2-propanol, 1-methoxy-2-propanol acetate, butyl cellosolve, ethyl lactate, methyl lactate, diacetone alcohol, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, propyl acetate, butyl acetate, cyclohexyl acetate, etc. The solvent may be one kind or a combination of two or more kinds.
[0154] The temperature at which the coating film irradiated with radiation is heat-treated is more preferably 50 to 300° C., and further preferably 120 to 250° C. The time for the heat treatment is preferably 1 to 30 minutes.
[0155] <Step (4): Step of manufacturing a liquid crystal cell>
[0156] As described above, two substrates on which liquid crystal alignment films are formed are prepared, and liquid crystal is arranged between the two substrates arranged to face each other. Specifically, the following two methods can be cited.
[0157] In the first method, two substrates are first arranged oppositely with a gap (cell gap) between the two liquid crystal alignment films. Next, the peripheries of the two substrates are bonded together using a sealant, and a liquid crystal composition is injected into the cell gap defined by the substrate surface and the sealant, and after the liquid crystal composition contacts the film surface, the injection hole is sealed.
[0158] In addition, the second method is a method called ODF (One Drop Fill: liquid crystal dripping) method. For example, a UV-curable sealant is applied to a specified position on one of the two substrates on which a liquid crystal alignment film is formed, and a liquid crystal composition is further dripped into several specified positions on the surface of the liquid crystal alignment film. Then, the substrate of the other side is bonded in a manner that the liquid crystal alignment film is opposite, and the liquid crystal composition is extended to the entire surface of the substrate and contacts the film surface. Then, ultraviolet light is irradiated on the entire surface of the substrate to cure the sealant. Regardless of which method is used, it is ideal that after further heating to a temperature at which the liquid crystal composition used becomes an isotropic phase, it is slowly cooled to room temperature, thereby removing the flow orientation during liquid crystal filling.
[0159] In addition, when the coating film is subjected to a rubbing orientation treatment, the two substrates are disposed facing each other so that the rubbing directions of the coating films form a predetermined angle, for example, orthogonal or antiparallel.
[0160] As the sealant, for example, an epoxy resin containing a curing agent and alumina balls as spacers can be used.
[0161] As the above-mentioned liquid crystal composition, there is no particular limitation, and it is a composition comprising at least one liquid crystal compound (liquid crystal molecule), and examples thereof include: a liquid crystal composition in a nematic phase (hereinafter, also referred to as a nematic phase liquid crystal), a liquid crystal composition in a smectic phase, or a liquid crystal composition in a cholesteric phase, wherein a nematic phase liquid crystal is preferred. In addition, various liquid crystal compositions having a positive or negative dielectric anisotropy can be used. It should be noted that, hereinafter, a liquid crystal composition having a positive dielectric anisotropy is also referred to as a positive liquid crystal, and a liquid crystal composition having a negative dielectric anisotropy is also referred to as a negative liquid crystal.
[0162] The above-mentioned liquid crystal composition may contain liquid crystal compounds having fluorine atoms, hydroxyl groups, amino groups, fluorine-containing groups (such as trifluoromethyl groups), cyano groups, alkyl groups, alkoxy groups, alkenyl groups, isothiocyanate groups, heterocyclic rings, cycloalkanes, cycloalkenes, steroid skeletons, benzene rings or naphthalene rings, and may also contain compounds having two or more rigid sites (mesogenic skeletons) that embody liquid crystal properties in the molecule (for example, a bi-mesogenic compound formed by two rigid biphenyl structures or terphenyl structures linked by an alkyl group).
[0163] In addition, from the perspective of improving the orientation of the liquid crystal, the liquid crystal composition may further contain additives. Such additives include: photopolymerizable monomers such as compounds having polymerizable groups; optically active compounds (e.g., S-811 manufactured by Merck, Inc.); antioxidants; ultraviolet absorbers; pigments; defoamers; polymerization initiators; or polymerization inhibitors.
[0164] Examples of the positive liquid crystal include ZLI-2293, ZLI-4792, MLC-2003, MLC-2041, MLC-3019, and MLC-7081 manufactured by Merck.
[0165] As a negative liquid crystal, MLC-6608, MLC-6609, MLC-6610, MLC-7026, or MLC-7026-100 manufactured by Merck is mentioned, for example.
[0166] Moreover, as a liquid crystal containing the compound which has a polymerizable group, MLC-3023 manufactured by Merck can be mentioned.
[0167] The liquid crystal alignment agent of the present invention is also preferably used for a liquid crystal display element (PSA-type liquid crystal display element) having a liquid crystal layer between a pair of substrates having electrodes, which is manufactured by the following process: a liquid crystal composition containing a polymerizable compound that is polymerized by at least one of active energy rays and heat is arranged between a pair of substrates, a voltage is applied between the electrodes, and the polymerizable compound is polymerized by at least one of irradiation with active energy rays and heating.
[0168] In addition, the liquid crystal alignment agent of the present invention is also preferably used for a liquid crystal display element (SC-PVA mode type liquid crystal display element) having a liquid crystal layer between a pair of substrates having electrodes, which is manufactured by the following process: a liquid crystal alignment film containing a polymerizable group that is polymerized by at least one of active energy rays and heat is arranged between the above-mentioned pair of substrates, and a voltage is applied between the electrodes.
[0169] <Step (4-2): Case of PSA Type Liquid Crystal Display Element>
[0170] The same method as in (4) is carried out except that a liquid crystal composition containing a polymerizable compound is injected or dropped. Examples of the polymerizable compound include polymerizable compounds having one or more polymerizable unsaturated groups such as acrylate groups and methacrylate groups in the molecule.
[0171] <Step (4-3): In the case of SC-PVA mode liquid crystal display element>
[0172] It is also possible to adopt a method for manufacturing a liquid crystal display element by carrying out the same process as the above (4) and then irradiating it with ultraviolet rays as described later. According to this method, as in the case of manufacturing the above-mentioned PSA-type liquid crystal display element, a liquid crystal display element with excellent response speed under a small amount of light irradiation can be obtained. The compound having a polymerizable group can be a compound having one or more of the above-mentioned polymerizable unsaturated groups in the molecule, and its content is preferably 0.1 to 30 parts by mass, more preferably 1 to 20 parts by mass relative to 100 parts by mass of all polymer components. In addition, the above-mentioned polymerizable group can also be present in a polymer used for a liquid crystal aligning agent. As such a polymer, for example, a polymer obtained by reacting a diamine component containing a diamine having the above-mentioned photopolymerizable group at the end can be listed.
[0173] <Step (4-4): Ultraviolet irradiation step>
[0174] The liquid crystal box is irradiated with light while a voltage is applied between the conductive films of a pair of substrates obtained in (4-2) or (4-3) above. The voltage applied here can be set to, for example, a direct current or alternating current of 5 to 50 V. In addition, as the irradiation light, for example, ultraviolet light and visible light containing a wavelength of 150 to 800 nm can be used, preferably ultraviolet light containing a wavelength of 300 to 400 nm. As the light source of the irradiation light, for example, a low-pressure mercury lamp, a high-pressure mercury lamp, a deuterium lamp, a metal halide lamp, an argon resonance lamp, a xenon lamp, an excimer laser, etc. can be used. The irradiation amount of light is preferably 1000 to 200,000 J / m 2 , more preferably 1000 to 100000 J / m 2 .
[0175] Furthermore, a liquid crystal display element can be obtained by attaching a polarizing plate to the outer surface of a liquid crystal cell as required. Examples of the polarizing plate attached to the outer surface of the liquid crystal cell include a polarizing plate formed by sandwiching a polarizing film called an "H film" between cellulose acetate protective films, or a polarizing plate composed of the H film itself, wherein the H film is formed by absorbing iodine while stretching and aligning polyvinyl alcohol.
[0176] Example
[0177] The present invention will be described in further detail below with reference to Examples, but the present invention is not limited to these Examples. The abbreviations of the compounds used and the methods for measuring the properties are as follows.
[0178] (Tetracarboxylic dianhydride)
[0179] CA-1 to CA-6: compounds represented by the following formulas (CA-1) to (CA-6), respectively.
[0180]
[0181] (Specific diamine)
[0182] DA-W1 to DA-W6: compounds represented by the following formulae (DA-W1) to (DA-W6), respectively (it should be noted that the compounds represented by the following formulae (DA-W1) to (DA-W6) and the above formula (DA-W1) A -1)~(d A -6) is the same as the diamine shown.
[0183]
[0184] (Other diamines)
[0185] DA-1 to DA-9: compounds represented by the following formulae (DA-1) to (DA-9), respectively.
[0186]
[0187] (additive)
[0188] AD-1 to AD-3: compounds represented by the following formulae (AD-1) to (AD-3), respectively.
[0189]
[0190] (Solvent)
[0191] NMP: N-methyl-2-pyrrolidone.
[0192] GBL: gamma-butyrolactone.
[0193] BCS: ethylene glycol monobutyl ether.
[0194] AcOEt: ethyl acetate.
[0195] MeCN: acetonitrile.
[0196] THF: tetrahydrofuran.
[0197] CHCl3: chloroform.
[0198] [Viscosity measurement]
[0199] The measurement was performed at a temperature of 25° C. using an E-type viscometer TVE-22H (manufactured by Toki Sangyo Co., Ltd.) with a sample amount of 1.1 mL and a conical rotor TE-1 (1°34′, R24).
[0200] [Determination of molecular weight]
[0201] The content was measured using the following normal temperature GPC (gel permeation chromatography) apparatus and calculated as a value converted to polyethylene glycol or polyethylene oxide.
[0202] GPC apparatus: SSC-7200 (manufactured by Senshu Scientific Co., Ltd.), chromatographic columns: GPC KD-803, GPCKD-805 (manufactured by Showa Denko Co., Ltd.) connected in series, chromatographic column temperature: 50°C, eluent: N,N-dimethylformamide (as additives, lithium bromide monohydrate (LiBr·H2O) is 30 mmol / L, phosphoric acid·anhydrous crystals (o-phosphoric acid) is 30 mmol / L, tetrahydrofuran (THF) is 10 mL / L), flow rate: 1.0 mL / min.
[0203] Standard samples for preparing the calibration curve: TSK standard polyethylene oxide (molecular weight: about 900,000, 150,000, 100,000 and 30,000) (manufactured by TOSOH) and polyethylene glycol (molecular weight: about 12,000, 4,000 and 1,000) (manufactured by Polymer Laboratories).
[0204] [Synthesis of Monomer]
[0205] DA-W1 to DA-W6 are novel compounds not disclosed in literature or the like, and their synthesis methods are described in detail below.
[0206] < 1 H-NMR measurement>
[0207] Apparatus: Fourier transform superconducting nuclear magnetic resonance apparatus (FT-NMR) "AVANCE III" (manufactured by BRUKER), 500 MHz.
[0208] Solvent: deuterated N,N-dimethyl sulfoxide ([D6]-DMSO).
[0209] Standard substance: tetramethylsilane (TMS).
[0210] <Example 1-1 Synthesis of [DA-W1]>
[0211]
[0212] After adding 4-(4-tert-butoxycarbonylaminophenylamino)aniline (37.6 g, 126 mmol) and NMP (380 g) to a 1L four-necked flask, CA-3 (18.5 g, 63.0 mmol) was added to the four-necked flask in a water bath, and the mixture was stirred at room temperature to react. After confirming the disappearance of the amino group by NMR, the reaction solution was injected into AcOEt (2000 g), and the organic layer was washed with pure water (1000 g) and concentrated. After adding pyridine (28.8 g, 364 mmol), acetic anhydride (18.6 g, 182 mmol) and NMP (500 g) to the obtained crude product, the mixture was stirred at 60°C to react. After the reaction was completed, the reaction solution was injected into pure water (2500 g) and the precipitate was filtered out. MeCN (800 g) was added to the obtained crude product, and repulping washing was performed at room temperature. Furthermore, THF (700 g) was added to the crude product to completely dissolve it, and the mixture was concentrated until precipitation occurred. AcOEt (300 g) was added, and the mixture was reslurried and washed at room temperature to obtain [DA-W1-1] (42.7 g, 49.8 mmol, yield: 79%).
[0213] After adding [DA-W1-1] (39.7 g, 46.3 mmol), 12 N hydrochloric acid (6.8 g) and AcOEt (1190 g) to a 2L four-necked flask, the mixture was stirred at 60°C to react. After the reaction was completed, the precipitate was filtered out, and MeCN (500 g) was added to the obtained crude product. The mixture was neutralized with triethylamine until it became alkaline, and the precipitate was filtered out. DMF (90 g) was added to the obtained crude product, and after it was completely dissolved, MeCN (600 g) was added to precipitate the solid. The precipitate was filtered out, and MeCN (600 g) was added to the crude product again. The mixture was re-pulped and washed at 80°C to obtain the target [DA-W1] (brown solid) (30.4 g, 46.3 mmol, yield: 100%). 1 The results of H-NMR are shown below. From these results, it was confirmed that the obtained solid was the target [DA-W1].
[0214] 1 H-NMR (500MHz, [D6]-DMSO): δ (ppm) = 8.33-8.36 (m, 4H), 8.04-8.06 (d, 2H), 7.7 6(s, 2H), 7.13-7.15(d, 4H), 6.85-6.90(m, 8H), 6.58-6.59(d, 4H), 4.90(s, 4H).
[0215] <Synthesis of Example 1-2 [DA-W2]>
[0216]
[0217] After adding 4,4'-diaminodiphenyl-N-methylamine (128 g, 600 mmol) and THF (1900 g) to a 3L four-necked flask, di-tert-butyl dicarbonate (43.7 g, 200 mmol) was added dropwise to the four-necked flask in a water bath, and the mixture was stirred at room temperature to react. After the reaction was completed, the reaction solution was concentrated, and the obtained residue was isolated by silica gel column chromatography (ethyl acetate: hexane = 1: 1 (volume ratio)), thereby obtaining [DA-W2-1] (55.5 g, 177 mmol, yield: 89%).
[0218] After adding [DA-W2-1] (55.5 g, 177 mmol) and NMP (550 g) to a 1L four-necked flask, CA-3 (26.0 g, 89 mmol) was added to the four-necked flask in a water bath, and the mixture was stirred at room temperature to react. After confirming the disappearance of the amino group by NMR, pyridine (42.0 g, 531 mmol) and acetic anhydride (27.1 g, 266 mmol) were added to the reaction solution, and the mixture was stirred at 60°C to react. After the reaction was completed, the reaction solution was injected into pure water (2500 g) and the precipitate was filtered out. AcOEt (1000 g) was added to the obtained crude product, and the mixture was re-pulped and washed at 70°C to obtain [DA-W2-2] (36.3 g, 41.0 mmol, yield: 92%).
[0219] After adding [DA-W2-2] (36.3 g, 41.0 mmol), 12 N hydrochloric acid (16.7 g) and AcOEt (720 g) to a 3L four-necked flask, the mixture was stirred at 70°C to react. After the reaction was completed, the precipitate was filtered out, and MeCN (600 g) was added to the obtained crude product. The mixture was neutralized with triethylamine until it became alkaline, and the precipitate was filtered out. NMP (60 g) was added to the obtained crude product, and after it was completely dissolved, it was injected into MeCN (800 g). The precipitate was filtered out, and MeCN (300 g) was added to the crude product again. The mixture was re-pulped and washed at 80°C to obtain the target [DA-W2] (brown solid) (25.8 g, 37.7 mmol, yield: 92%). 1 The results of H-NMR are shown below. From these results, it was confirmed that the obtained solid was the target [DA-W2].
[0220] 1H-NMR (500MHz, [D6]-DMSO): δ (ppm) = 8.33-8.36 (m, 4H), 8.04-8.05 (d, 2H), 7.15-7.17 (d , 4H), 6.90-6.92(d, 4H), 6.68-6.70(d, 4H), 6.62-6.64(d, 4H), 5.08(s, 4H), 3.19(s, 6H).
[0221] <Synthesis of Example 1-3 [DA-W3]>
[0222]
[0223] After adding 4-(4-tert-butoxycarbonylaminophenylamino)aniline (29.9 g, 100 mmol) and NMP (300 g) to a 500 mL four-necked flask, CA-6 (9.82 g, 45.0 mmol) was added to the four-necked flask in a water bath, and the mixture was stirred at room temperature to react. After confirming the disappearance of the amino group by NMR, the reaction solution was injected into AcOEt (1000 g), and the organic layer was washed with pure water (1000 g) and concentrated. After adding pyridine (21.4 g, 270 mmol), acetic anhydride (13.8 g, 135 mmol) and NMP (370 g) to the obtained crude product, the mixture was stirred at 60°C to react. After the reaction was completed, the reaction solution was injected into MeCN (2000 g) and the precipitate was filtered out. MeCN (500 g) was added to the obtained precipitate, and reslurry washing was performed at 70° C., thereby obtaining [DA-W3-1] (29.9 g, 38.3 mmol, yield: 85%).
[0224] After adding [DA-W3-1] (29.9 g, 38.3 mmol), 12 N hydrochloric acid (15.0 g) and AcOEt (600 g) to a 2L four-necked flask, the mixture was stirred at 60°C to react. After the reaction was completed, the precipitate was filtered out, and NMP (500 g) was added to the obtained crude product. The product was neutralized with triethylamine until it became alkaline, and the precipitate was filtered out. MeCN (2500 g) was added to the obtained crude product, and the product was re-pulped and washed at room temperature to obtain the target [DA-W3] (dark brown solid) (17.3 g, 29.8 mmol, yield: 78%). 1 The results of H-NMR are shown below. From these results, it was confirmed that the obtained solid was the target [DA-W3].
[0225] 1H-NMR (500MHz, [D6]-DMSO): δ (ppm) = 8.28 (s, 2H), 7.78 (s, 2H), 7.16-7.18 (d, 4H), 6.84-6.90 (m, 8H), 6.57-6.59 (d, 4H), 4.84 (s, 4H).
[0226] <Synthesis of Example 1-4 [DA-W4]>
[0227]
[0228] After adding [DA-W2-1] (22.1 g, 70.5 mmol) and NMP (220 g) to a 500 mL four-necked flask, CA-6 (7.70 g, 35.3 mmol) was added to the four-necked flask in a water bath, and the mixture was stirred at room temperature to react. After confirming the disappearance of the amino group by NMR, pyridine (16.7 g, 211 mmol) and acetic anhydride (10.7 g, 106 mmol) were added to the reaction solution, and the mixture was stirred at 50°C to react. After the reaction was completed, the reaction solution was poured into pure water (1500 g) and the precipitate was filtered out. MeCN (500 g) was added to the obtained crude product, and the mixture was re-pulped and washed at 70°C to obtain [DA-W4-1] (24.5 g, 30.3 mmol, yield: 86%).
[0229] After adding [DA-W4-1] (24.5 g, 30.3 mmol), trifluoroacetic acid (34.2 g, 300 mmol) and CHCl3 (250 g) to a 500 mL four-necked flask, stir and react at 50°C. After the reaction is completed, inject the reaction solution into hexane (250 g) and filter out the precipitate. Add THF (450 g) to the obtained crude product, neutralize it with triethylamine until it becomes alkaline, and filter out the precipitate. Add THF (450 g) to the obtained crude product, re-pulp and wash it at 60°C, thereby obtaining the target [DA-W4] (brown solid) (17.6 g, 28.9 mmol, yield: 95%). 1 The results of H-NMR are shown below. From these results, it was confirmed that the obtained solid was the target [DA-W4].
[0230] 1 H-NMR (500MHz, [D6]-DMSO): δ (ppm) = 8.27 (s, 2H), 7.18-7.19 (d, 4H), 6.90-6 .92 (d, 4H), 6.68-6.70 (d, 4H), 6.62-6.64 (d, 4H), 5.09 (s, 4H), 3.31 (s, 6H).
[0231] <Synthesis of Example 1-5 [DA-W5]>
[0232]
[0233] After adding 4-(4-tert-butoxycarbonylaminophenylamino)aniline (12.0 g, 40.0 mmol) and NMP (120 g) to a 1L four-necked flask, CA-5 (6.44 g, 20.0 mmol) was added to the four-necked flask in a water bath, and the mixture was stirred at room temperature to react. After confirming the disappearance of the amino group by NMR, the reaction solution was injected into AcOEt (600 g), and the organic layer was washed with pure water (400 g) and concentrated. After adding pyridine (9.5 g, 120 mmol), acetic anhydride (6.1 g, 60 mmol) and NMP (180 g) to the obtained crude product, the mixture was stirred at 60°C to react. After the reaction was completed, the reaction solution was injected into MeCN (1000 g) and the precipitate was filtered out. MeCN (500 g) was added to the obtained precipitate, and reslurry washing was performed at room temperature to obtain [DA-W5-1] (15.8 g, 17.9 mmol, yield: 90%).
[0234] After adding [DA-W5-1] (15.8 g, 17.9 mmol), 12 N hydrochloric acid (7.0 g) and AcOEt (320 g) to a 1L four-necked flask, the mixture was stirred at 70°C to react. After the reaction was completed, the precipitate was filtered out, MeCN (400 g) was added to the crude product, and the mixture was neutralized with triethylamine until it became alkaline, and the precipitate was filtered out. NMP (150 g) was added to the crude product to completely dissolve it, and then MeCN (400 g) was added. The precipitate was filtered out, and MeCN (250 g) was added to the crude product again, and the mixture was re-pulped and washed at 80°C to obtain the target [DA-W5] (red-purple solid) (11.5 g, 16.8 mmol, yield: 94%). 1 The results of H-NMR are shown below. From these results, it was confirmed that the obtained solid was the target [DA-W5].
[0235] 1 H-NMR (500MHz, [D6]-DMSO): δ (ppm) = 8.23-8.25 (m, 2H), 8.13-8.14 (m, 4H), 7.7 6(s, 2H), 7.13-7.15(d, 4H), 6.84-6.89(m, 8H), 6.57-6.59(d, 4H), 4.89(s, 4H).
[0236] <Synthesis of Example 1-6 [DA-W6]>
[0237]
[0238] After adding [DA-W2-1] (11.5 g, 36.7 mmol) and NMP (120 g) to a 300 mL four-necked flask, CA-5 (5.90 g, 18.3 mmol) was added to the four-necked flask in a water bath, and the mixture was stirred at room temperature to react. After confirming the disappearance of the amino group by NMR, the reaction solution was injected into AcOEt (500 g), and the organic layer was washed with pure water (400 g) and concentrated. After adding pyridine (8.70 g, 110 mmol), acetic anhydride (5.60 g, 55.3 mmol) and NMP (180 g) to the obtained crude product, the mixture was stirred at 60°C to react. After the reaction was completed, the reaction solution was injected into pure water (600 g) and the precipitate was filtered out. MeCN (500 g) was added to the obtained crude product, and reslurry washing was performed at room temperature to obtain [DA-W6-1] (16.1 g, 17.6 mmol, yield: 96%).
[0239] After adding [DA-W6-1] (16.1 g, 17.6 mmol), 12 equivalent hydrochloric acid (29.7 g) and AcOEt (320 g) to a 3L four-necked flask, the mixture was stirred at 70°C to react. After the reaction was completed, the precipitate was filtered out, and MeCN (700 g) was added to the obtained crude product. The mixture was neutralized with triethylamine until it became alkaline, and the precipitate was filtered out. NMP (60 g) was added to the obtained crude product, and after it was completely dissolved, it was injected into MeCN (360 g). The precipitate was filtered out, and MeCN (100 g) was added to the crude product again. The mixture was re-pulped and washed at 80°C to obtain the target [DA-W6] (brown solid) (5.5 g, 7.72 mmol, yield: 44%). 1 The results of H-NMR are shown below. From these results, it was confirmed that the obtained solid was the target [DA-W6].
[0240] 1 H-NMR (500MHz, [D6]-DMSO): δ (ppm) = 8.22-8.24 (d, 2H), 8.12-8.14 (m, 4H), 7.15-7.17 (d , 4H), 6.90-6.91(d, 4H), 6.68-6.70(d, 4H), 6.61-6.63(d, 4H), 5.09(s, 4H), 3.19(s, 6H).
[0241] [Synthesis of polymer]
[0242] <Example 2-1>
[0243] DA-W1 (2.56 g, 3.90 mmol), DA-4 (0.626 g, 2.10 mmol) and NMP (28.7 g) were added to a 50 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and stirred at room temperature to dissolve while nitrogen was supplied. Then, CA-1 (0.977 g, 4.98 mmol) and NMP (1.85 g) were added and stirred at room temperature for 2 hours to obtain a solution of polyamic acid (PAA-A1) with a solid content concentration of 12% by mass (viscosity: 563 mPa·s).
[0244] <Example 2-2>
[0245] DA-W1 (2.15 g, 3.28 mmol), DA-4 (0.734 g, 2.46 mmol), DA-8 (1.04 g, 2.46 mmol) and NMP (35.3 g) were added to a 50 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and stirred at room temperature to dissolve while nitrogen was supplied. Then, CA-1 (1.42 g, 7.23 mmol) and NMP (3.86 g) were added and stirred at room temperature for 2 hours to obtain a solution of polyamic acid (PAA-A2) with a solid content concentration of 12% by mass (viscosity: 402 mPa·s).
[0246] <Example 2-3>
[0247] DA-W1 (2.99 g, 4.55 mmol), DA-4 (0.731 g, 2.45 mmol) and NMP (27.3 g) were added to a 50 mL four-necked flask with a stirring device and a nitrogen inlet tube, and stirred at room temperature to dissolve while supplying nitrogen. Then, CA-1 (0.153 g, 0.781 mmol) and NMP (1.13 g) were added and stirred at room temperature for 1 hour. Then, CA-2 (1.31 g, 5.25 mmol) and NMP (9.63 g) were added and stirred at 50°C for 12 hours to obtain a solution of polyamic acid (PAA-A3) with a solid content concentration of 12% by mass (viscosity: 396 mPa·s).
[0248] <Example 2-4>
[0249] DA-W2 (2.67 g, 3.90 mmol), DA-4 (0.627 g, 2.10 mmol) and NMP (30.1 g) were added to a 50 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and stirred at room temperature to dissolve while nitrogen was supplied. Then, CA-1 (1.06 g, 5.40 mmol) and NMP (2.26 g) were added and stirred at room temperature for 2 hours to obtain a solution of polyamic acid (PAA-A4) with a solid content concentration of 12% by mass (viscosity: 411 mPa·s).
[0250] <Example 2-5>
[0251] DA-W2 (2.25 g, 3.28 mmol), DA-4 (0.734 g, 2.46 mmol), DA-8 (1.04 g, 2.46 mmol) and NMP (36.2 g) were added to a 50 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and stirred at room temperature to dissolve while nitrogen was supplied. Then, CA-1 (1.50 g, 7.67 mmol) and NMP (4.33 g) were added and stirred at room temperature for 2 hours to obtain a solution of polyamic acid (PAA-A5) having a solid content concentration of 12% by mass (viscosity: 396 mPa·s).
[0252] <Example 2-6>
[0253] DA-W3 (1.89 g, 3.25 mmol), DA-4 (0.522 g, 1.75 mmol) and NMP (25.9 g) were added to a 50 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and stirred at room temperature to dissolve while nitrogen was supplied. Then, CA-1 (0.804 g, 4.10 mmol) and NMP (2.99 g) were added and stirred at room temperature for 2 hours to obtain a solution of polyamic acid (PAA-A6) with a solid content concentration of 10% by mass (viscosity: 237 mPa·s).
[0254] <Example 2-7>
[0255] DA-W4 (2.37 g, 3.90 mmol), DA-4 (0.627 g, 2.10 mmol) and NMP (27.0 g) were added to a 50 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and stirred at room temperature to dissolve while nitrogen was supplied. Then, CA-1 (1.02 g, 5.22 mmol) and NMP (2.49 g) were added and stirred at room temperature for 2 hours to obtain a solution of polyamic acid (PAA-A7) with a solid content concentration of 12% by mass (viscosity: 413 mPa·s).
[0256] <Comparative Example 2-1>
[0257] DA-7 (3.79 g, 19.0 mmol), DA-4 (1.42 g, 4.76 mmol) and NMP (46.9 g) were added to a 50 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and stirred at room temperature to dissolve while supplying nitrogen. Then, CA-3 (2.80 g, 9.52 mmol) and NMP (11.9 g) were added and stirred at 70°C for 4 hours. Then, CA-1 (2.52 g, 12.8 mmol) and NMP (18.5 g) were added and stirred at room temperature for 2 hours to obtain a solution of polyamic acid (PAA-B1) with a solid content concentration of 12% by mass (viscosity: 423 mPa·s).
[0258] <Comparative Example 2-2>
[0259] DA-7 (2.85 g, 14.3 mmol), DA-4 (1.42 g, 4.76 mmol), DA-8 (2.01 g, 4.76 mmol) and NMP (56.5 g) were added to a 50 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and stirred at room temperature to dissolve while supplying nitrogen. Then, CA-3 (2.80 g, 9.52 mmol) and NMP (10.1 g) were added, and stirred at 70°C for 4 hours. Then, CA-1 (2.58 g, 13.2 mmol) and NMP (18.9 g) were added, and stirred at room temperature for 2 hours, thereby obtaining a solution of polyamic acid (PAA-B2) having a solid content concentration of 12% by mass (viscosity: 378 mPa·s).
[0260] <Comparative Examples 2-3>
[0261] DA-7 (3.79 g, 19.0 mmol), DA-4 (1.42 g, 4.76 mmol) and NMP (46.9 g) were added to a 50 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and stirred at room temperature to dissolve while supplying nitrogen. Then, CA-3 (2.80 g, 9.52 mmol) and NMP (11.9 g) were added, and stirred at 70°C for 4 hours. Then, CA-1 (0.513 g, 2.62 mmol) and NMP (3.76 g) were added, and stirred at room temperature for 1 hour. Then, CA-2 (2.68 g, 10.7 mmol) and NMP (19.6 g) were added, and stirred at 50°C for 12 hours, thereby obtaining a solution of polyamic acid (PAA-B3) having a solid content concentration of 12% by mass (viscosity: 410 mPa·s).
[0262] <Preparation Example 2-1>
[0263] DA-1 (0.540 g, 4.99 mmol), DA-2 (1.83 g, 7.49 mmol), DA-3 (2.40 g, 7.49 mmol), DA-5 (1.99 g, 4.99 mmol) and NMP (68.4 g) were added to a 50 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and stirred at room temperature to dissolve while nitrogen was supplied. Then, CA-4 (5.31 g, 23.7 mmol) and NMP (20.1 g) were added, and stirred at 50° C. for 12 hours to obtain a solution of polyamic acid (PAA-U1) having a solid content concentration of 12% by mass (viscosity: 402 mPa·s).
[0264] <Preparation Example 2-2>
[0265] DA-1 (1.62 g, 15.0 mmol), DA-2 (2.20 g, 9.01 mmol), DA-6 (2.04 g, 5.97 mmol) and NMP (59.3 g) were added to a 100 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and stirred at room temperature to dissolve while nitrogen was supplied. Then, CA-4 (6.32 g, 28.2 mmol) and NMP (30.0 g) were added, and stirred at 40° C. for 3 hours to obtain a solution of polyamic acid (PAA-U2) having a solid content concentration of 12% by mass (viscosity: 220 mPa·s).
[0266] <Preparation Example 2-3>
[0267] DA-7 (4.78 g, 24.0 mmol), DA-4 (2.39 g, 8.01 mmol), DA-8 (3.37 g, 7.99 mmol) and NMP (77.3 g) were added to a 100 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and stirred at room temperature to dissolve while nitrogen was supplied. Then, CA-3 (11.3 g, 38.4 mmol) and NMP (82.9 g) were added, and stirred at 70° C. for 24 hours to obtain a solution of polyamic acid (PAA-C1) having a solid content concentration of 12% by mass.
[0268] <Preparation Example 2-4>
[0269] DA-7 (2.55 g, 12.8 mmol), DA-9 (0.487 g, 3.20 mmol) and NMP (22.3 g) were added to a 50 mL four-necked flask equipped with a stirring device and a nitrogen inlet tube, and stirred at room temperature to dissolve while nitrogen was supplied. Then, CA-3 (4.50 g, 15.3 mmol) and NMP (20.5 g) were added, and stirred at 50° C. for 16 hours to obtain a solution of polyamic acid (PAA-C2) with a solid content concentration of 15% by mass (viscosity: 350 mPa·s).
[0270] The specifications of the polyamic acid obtained in the above synthesis example are shown in Table 1. In the table, the numerical values in parentheses of the tetracarboxylic acid component and the diamine component represent the amount (parts by mole) of each tetracarboxylic acid component or each diamine used per 100 parts by mole of the total amount of the diamine component used in the polymerization.
[0271] [Table 1]
[0272]
[0273] Here, the specific diamine DA-W1 is a structure obtained by reacting one molecule of tetracarboxylic dianhydride CA-3 with two molecules of diamine DA-7. The synthesis of the polyamic acid PAA-A1 of Example 2-1 corresponds to the reaction using monomer components containing 4.98 mmol of CA-1, 3.90 mmol of CA-3, 7.80 mmol of DA-7, and 2.10 mmol of DA-4.
[0274] Among the above monomer components, when the total of DA-4 and DA-7 is 100 parts by mole, the molar ratio of each monomer component is 50 parts by mole of CA-1, 39 parts by mole of CA-3, 79 parts by mole of DA-7, and 21 parts by mole of DA-4, which is substantially the same monomer composition as the polyamic acid PAA-B1 of Comparative Example 2-1. On the other hand, the polyamic acid PAA-A1 of Example 2-1 is a polymer having an imide structure, and the imide structure exists at adjacent positions, while the polyamic acid PAA-B1 of Comparative Example 2-1 is a polymer having only an amic acid structure, and the obtained liquid crystal alignment film has different properties as described later.
[0275] Similarly, polyamic acids PAA-A2 to PAA-A3 have substantially the same monomer compositions as those of polyamic acids PAA-B2 to PAA-B3, respectively.
[0276] [Preparation of Liquid Crystal Alignment Agent]
[0277] <Example 3-1>
[0278] The solution of the polyamic acid (PAA-A1) obtained in Example 2-1 was diluted with NMP, GBL, and BCS, and stirred at room temperature for 2 hours to obtain a liquid crystal aligning agent (AL-1) having a mass ratio of polymer solid content to each solvent (polymer solid content: NMP: GBL: BCS) of 4.5:45.5:30:20.
[0279] <Examples 3-2 to 3-3, Comparative Examples 3-1 to 3-3>
[0280] As shown in Table 2, liquid crystal aligning agents (AL-2) to (AL-3) and (AL-C1) to (AL-C3) were obtained in the same manner as in Example 3-1, except that the polyamic acid used was replaced by PAA-A2 to PAA-A3 and PAA-B1 to PAA-B3 from PAA-A1.
[0281] <Examples 3-4>
[0282] The solution of the polyamic acid (PAA-U1) obtained in Preparation Example 2-1 and the solution of the polyamic acid (PAA-A1) obtained in Example 2-1 were diluted with NMP, GBL and BCS, and stirred at room temperature for 2 hours to obtain a liquid crystal aligning agent (AL-4) having a polymer solid content ratio (PAA-U1:PAA-A1) of 5:5 and a mass ratio of the total solid content of the polymer to each solvent (polymer solid content: NMP:GBL:BCS) of 5.5:44.5:30:20.
[0283] <Examples 3-5 to 3-6>
[0284] As shown in Table 2, liquid crystal aligning agents (AL-5) to (AL-6) were obtained in the same manner as in Example 3-4, except that the polyamic acid to be used was replaced with PAA-A2 to PAA-A3 from PAA-A1.
[0285] <Examples 3-7>
[0286] The solution of the polyamic acid (PAA-U1) obtained in Preparation Example 2-1 and the solution of the polyamic acid (PAA-A1) obtained in Example 2-1 were used, diluted with NMP, GBL and BCS, and AD-1 was further added, and stirred at room temperature for 2 hours, thereby obtaining a liquid crystal aligning agent (AL-7) in which the solid content ratio of the polymer (PAA-U1:PAA-A1) was 5:5, the mass ratio of the total solid content of the polymer to each solvent (polymer solid content: NMP:GBL:BCS) was 5.5:44.5:30:20, and the mixing ratio of AD-1 was 5 parts by mass relative to 100 parts by mass of the total amount of the polymer.
[0287] <Examples 3-8 to 3-11, Comparative Example 3-4>
[0288] As shown in Table 2, liquid crystal aligning agents (AL-8) to (AL-11) and (AL-C4) were obtained in the same manner as in Example 3-7, except that the polyamic acid used was replaced with PAA-A2 to PAA-A5 and PAA-C1 from PAA-A1.
[0289] <Comparative Examples 3-5>
[0290] The solution of the polyamic acid (PAA-U2) obtained in Preparation Example 2-2 and the solution of the polyamic acid (PAA-C2) obtained in Preparation Example 2-4 were used, diluted with NMP, GBL and BCS, and AD-1 to AD-3 were further added, and stirred at room temperature for 2 hours to obtain a liquid crystal aligning agent (AL-C5) having a polymer solid content ratio (PAA-U2:PAA-C2) of 3:7, a mass ratio of the total solid content of the polymer to each solvent (polymer solid content:NMP:GBL:BCS) of 5.5:44.5:30:20, and the mixing ratios of AD-1, AD-2, and AD-3 were 5 mass parts, 1 mass part, and 14 mass parts, respectively, relative to 100 mass parts of the total amount of the polymer.
[0291] [Table 2]
[0292]
[0293] In the table, the values in brackets of polyamic acid represent the content (mass parts) of each polyamic acid relative to 100 parts by mass of the total amount of polymers contained in each liquid crystal aligning agent. The values in brackets of additives represent the content (mass parts) of each additive relative to 100 parts by mass of the total amount of polymers contained in each liquid crystal aligning agent.
[0294] [Production of Liquid Crystal Cell]
[0295] A liquid crystal cell having a structure of an FFS mode liquid crystal display element was produced.
[0296] First, prepare a substrate with electrodes. A glass substrate with a rectangular shape of 30 mm × 50 mm and a thickness of 0.7 mm is used as the substrate. An ITO electrode with a dense pattern constituting a counter electrode is formed on the substrate as the first layer, and a SiN (silicon nitride) film formed by CVD (chemical vapor deposition) is formed on the counter electrode of the first layer as the second layer. A SiN film with a thickness of 300 nm that functions as an interlayer insulating film is used as the second layer of the SiN film. A comb-shaped pixel electrode formed by patterning the ITO film is arranged on the second layer of the SiN film as the third layer, and two types of pixels, the first pixel and the second pixel, are formed, and the size of each pixel is 10 mm long and about 5 mm wide. At this time, the counter electrode of the first layer and the pixel electrode of the third layer are electrically insulated due to the action of the SiN film of the second layer.
[0297] The pixel electrode of the third layer has a comb-tooth shape in which multiple electrode elements with a width of 3 μm are arranged in parallel at intervals of 6 μm and the central part is bent at an internal angle of 160°. One pixel has a first area and a second area with a line connecting the bent parts of the multiple electrode elements as the boundary.
[0298] Next, the liquid crystal alignment agents AL-1 to AL11 and AL-C1 to AL-C5 obtained in the above-mentioned embodiments 3-1 to 3-11 and comparative examples 3-1 to 3-5 were filtered using a filter with a pore size of 1.0 μm, and then applied to the surface of the substrate with electrodes (first glass substrate) prepared above and the surface of a glass substrate (second glass substrate) with a columnar spacer having an ITO film formed on the back and a height of 4 μm. Next, after drying on a hot plate at 80°C for 2 minutes, the mixture was sintered in a hot air circulation oven at 230°C for 30 minutes to form a coating film with a thickness of 100 nm. The coating film surface was subjected to a polarizing plate at 300 mJ / cm 2The substrate with a liquid crystal alignment film was irradiated with ultraviolet light of a wavelength of 254 nm with linear polarization having an extinction ratio of 26:1, and an orientation treatment was performed to obtain a substrate with a liquid crystal alignment film. It should be noted that, for the liquid crystal alignment film formed on the substrate with electrodes, the orientation treatment was performed in a manner that the direction of bisecting the inner angle of the pixel bending portion was orthogonal to the orientation direction of the liquid crystal, and for the liquid crystal alignment film formed on the second glass substrate, the orientation treatment was performed in a manner that the orientation direction of the liquid crystal on the first glass substrate was consistent with the orientation direction of the liquid crystal on the second glass substrate when the liquid crystal box was made. The above two substrates were used as a set, leaving a liquid crystal injection port, printing a sealant (XN-1500T manufactured by Mitsui Chemicals Co., Ltd.) around it, and attaching another substrate in a manner that the liquid crystal alignment film faces each other and the orientation direction is 0°. Then, the sealant was cured to produce an empty box. Positive liquid crystal MLC-3019 (manufactured by Merck) was injected into the empty box by a reduced pressure injection method, and the injection port was sealed to obtain an FFS driven liquid crystal box. Then, the obtained liquid crystal box was heated at 110°C for 1 hour, and left overnight for evaluation.
[0299] [Evaluation of voltage holding ratio]
[0300] A voltage of 1V was applied to the FFS-driven liquid crystal box prepared in the above order at a temperature of 60°C for 60μsec, and the voltage after 1000msec was measured, and the voltage was calculated as the voltage holding ratio. VHR-1 manufactured by TOYO Corporation was used in the measurement of the voltage holding ratio. It should be noted that the higher the value of the voltage holding ratio, the better. The results are shown in Table 3.
[0301] [Evaluation of Liquid Crystal Orientation Stability]
[0302] This evaluation evaluated the afterimage (also referred to as AC afterimage) generated by the decrease in the alignment performance of the liquid crystal alignment film during long-term AC driving.
[0303] The FFS-driven liquid crystal box produced in the above is subjected to an AC voltage of ±4V at a frequency of 60Hz for 120 hours in a constant temperature environment of 60°C. Then, the pixel electrode and the opposing electrode of the liquid crystal box are short-circuited and kept in this state at room temperature for one day. For the liquid crystal box subjected to the above treatment, the deviation between the orientation direction of the liquid crystal in the first area of the pixel and the orientation direction of the liquid crystal in the second area in the state where no voltage is applied is calculated in the form of an angle. Specifically, the liquid crystal box is set between two polarizing plates arranged in an orthogonal manner with the polarization axes, the backlight is turned on, the configuration angle of the liquid crystal box is adjusted to minimize the intensity of the transmitted light in the first area of the first pixel, and then the rotation angle required to rotate the liquid crystal box to minimize the intensity of the transmitted light in the second area of the first pixel is calculated as the angle Δ. The same is true for the second pixel, and the first area is compared with the second area to calculate the same angle Δ. Then, the average value of the angle Δ between the first pixel and the second pixel is calculated as the rotation angle Δ of the liquid crystal box. It can be said that the smaller the value of the rotation angle Δ, the better the stability of the liquid crystal orientation. As evaluation criteria, the case where the rotation angle Δ of the liquid crystal cell obtained above was 0.10° or less was rated as “○”, and the case where the rotation angle Δ was greater than 0.10° was rated as “×”.
[0304] [Evaluation of film hardness]
[0305] The liquid crystal aligning agents AL-7 to AL-11 and AL-C4 to AL-C5 obtained in the above-mentioned Examples 3-7 to 3-11 and Comparative Examples 3-4 to 3-5 were respectively applied to the ITO substrate by spin coating. After drying on a hot plate at 80°C for 2 minutes, they were calcined in an IR oven at 230°C for 30 minutes to form a coating film with a thickness of 100 nm. The coating film surface was exposed to a polarizing plate at 300 mJ / cm 2 Irradiate ultraviolet rays with a wavelength of 254nm and linear polarization with an extinction ratio of 26:1, implement orientation treatment, and further sinter in an IR oven at 230°C for 30 minutes to obtain a substrate with a liquid crystal orientation film. Then, the liquid crystal orientation film was rubbed with a rayon cloth (YA-20R made by Yoshikawa Chemical Industry) (roller diameter: 120mm, roller rotation speed: 1000rpm, moving speed: 20mm / sec, pressing length: 0.5mm), and the haze (Haze) value (turbidity) of the film was evaluated using a haze meter (HZ-V3 made by SUGA Test Instruments). It can be said that the smaller the haze value, the less the film loss, that is, the higher the film hardness. As an evaluation standard, the case where the haze value is less than 0.20 is set to "○", and the case where the haze value is greater than 0.20 is set to "×". The results are shown in Table 3.
[0306] [Evaluation of molecular weight change before and after calcination]
[0307] The liquid crystal aligning agents AL-1 to AL-3 and AL-C1 to AL-C3 obtained in the above-mentioned Examples 3-1 to 3-3 and Comparative Examples 3-1 to 3-3 were respectively applied to the ITO substrate by spin coating. After drying on a hot plate at 80°C for 2 minutes, the coating was calcined in an IR oven at 230°C for 30 minutes to form a coating film with a thickness of 100 nm. The calcined coating film was scraped off, the molecular weight was measured, and the change in molecular weight before and after calcination was evaluated (weight average molecular weight after calcination ÷ weight average molecular weight before calcination × 100[%]). The results are shown in Table 3.
[0308] [Table 3]
[0309]
[0310] As shown in Table 3, the liquid crystal alignment film obtained by using the liquid crystal alignment agent of the diamine component containing the specific diamine suppresses the decrease in molecular weight during firing, and shows a high voltage holding rate even after being exposed to high temperature for a long time, compared with the liquid crystal alignment film obtained by using the liquid crystal alignment agent of the diamine component containing no specific diamine. In addition, the liquid crystal alignment film obtained by using the liquid crystal alignment agent of the diamine component containing the specific diamine shows high liquid crystal orientation stability and high film hardness.
[0311] Furthermore, it was found that when a polymer (B) obtained from a diamine component not containing a specific diamine is used in addition to a polymer (P) obtained from a diamine component containing a specific diamine in a liquid crystal aligning agent, the voltage holding ratio is further improved. (Comparison of Examples 3-1 to 3-3 with Examples 3-4 to 3-6)
[0312] It should be noted that the entire contents of the specification, claims, drawings, and abstract of Japanese Patent Application No. 2022-079186 filed on May 13, 2022 are incorporated herein by reference in their entirety and are incorporated as a disclosure of the specification of the present invention.
Claims
1. A diamine, wherein According to the following formula (d A -1)~(d A -6) in any expression, 2. A polymer, wherein The polymer is at least one selected from the group consisting of a polyimide precursor obtained using a diamine component containing the diamine according to claim 1 and a polyimide which is an imidation product of the polyimide precursor.
3. The polymer according to claim 2, wherein The diamine component further includes a diamine having at least one group selected from the group consisting of a urea bond, an amide bond, a carboxyl group, and a hydroxyl group in the molecule.
4. The polymer according to claim 2 or 3, in, The diamine according to claim 1 is used in an amount of 5 mol% or more based on the diamine component.
5. The polymer according to any one of claims 2 to 4, wherein The polymer is obtained by a polymerization reaction of the diamine component and a tetracarboxylic acid component, and the tetracarboxylic acid component contains tetracarboxylic dianhydride or a derivative thereof.
6. The polymer according to claim 5, wherein The tetracarboxylic dianhydride or a derivative thereof is a non-cyclic aliphatic tetracarboxylic dianhydride, alicyclic tetracarboxylic dianhydride, aromatic tetracarboxylic dianhydride, or a derivative thereof.
7. The polymer according to any one of claims 5 to 6, wherein The tetracarboxylic dianhydride or its derivative is the following substance: Non-cyclic aliphatic tetracarboxylic dianhydride as 1,2,3,4-butanetetracarboxylic dianhydride; 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-dichloro-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-difluoro-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-bis(trifluoromethyl)-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 3,3',4,4'-dicyclohexyltetracarboxylic dianhydride, 2,3,5-tricarboxycyclopentyl Alicyclic tetracarboxylic acid dianhydrides of acetic dianhydride, 4-(2,5-dioxotetrahydrofuran-3-yl)tetrahydronaphthalene-1,2-dicarboxylic acid dianhydride, 5-(2,5-dioxotetrahydrofuran-3-yl)-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 5-(2,5-dioxotetrahydrofuran-3-yl)-8-methyl-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic acid dianhydride, bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic acid dianhydride and 2,4,6,8-tetracarboxybicyclo[3.3.0]octane-2:4,6:8-dianhydride; Selected from pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 2,2',3,3'-biphenyl tetracarboxylic dianhydride, 4,4'- Aromatic tetracarboxylic dianhydrides of bis(3,4-dicarboxyphenoxy)-2,2-diphenylpropane dianhydride, ethylene glycol bis(trimellitic anhydride), 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 4,4'-carbonyldiphthalic anhydride, 4,4'-(1,4-phenylenedioxy)bis(phthalic anhydride) and 4,4'-(1,4-phenylenedimethylene)bis(phthalic anhydride); or Their derivatives.
8. A liquid crystal alignment agent, characterized in that: Contains the polymer according to any one of claims 2 to 7.
9. The liquid crystal alignment agent according to claim 8, wherein: It also contains a polymer B, which is selected from the group consisting of At least one of the group consisting of a polyimide precursor obtained from the diamine component of the diamine according to claim 1 and a polyimide which is an imidate of the polyimide precursor.
10. The liquid crystal alignment agent according to claim 9, wherein: The polymer B is obtained by a polymerization reaction of the diamine component and a tetracarboxylic acid component, and the tetracarboxylic acid component contains tetracarboxylic dianhydride or a derivative thereof.
11. The liquid crystal aligning agent according to any one of claims 8 to 10, wherein The liquid crystal alignment agent also contains at least one additive selected from the following compounds: at least one cross-linking compound selected from the group consisting of a cross-linking compound c-1 having the following substituents and a cross-linking compound c-2 having a polymerizable unsaturated group; a functional silane compound; a metal chelate compound; a curing accelerator; a surfactant; an antioxidant; a sensitizer; a preservative; a compound for adjusting the dielectric constant and resistance of the obtained liquid crystal alignment film; and a compound for promoting imidization, wherein the substituent is selected from at least one of an oxirane group, an oxetane group, a blocked isocyanate group, an oxazoline group, a cyclocarbonate group, a hydroxyl group and an alkoxy group. 12 . A liquid crystal alignment film obtained from the liquid crystal alignment agent according to claim 8 . 13 . A liquid crystal display element comprising the liquid crystal alignment film according to claim 12 .
14. A method for manufacturing a liquid crystal display element, comprising the following steps 1 to 3: Step 1: a step of applying the liquid crystal alignment agent according to any one of claims 8 to 11 onto a substrate; Step 2: a step of calcining the applied liquid crystal alignment agent to obtain a film; Step 3: a step of subjecting the film obtained in step 2 to an orientation treatment.
15. The method for manufacturing a liquid crystal display element according to claim 14, wherein: The alignment treatment is a photo-alignment treatment.
Citation Information
Patent Citations
Method for orienting liquid crystal
JP1997297313A
Liquid crystal aligning agent and liquid crystal display element
JP2010097188A
Battery
JP2022079186A
Material for liquid crystal alignment and liquid crystal displays made by using the same
WO2004021076A1
Liquid-crystal alignment agent, liquid-crystal alignment film, and liquid-crystal display element
WO2011132751A1